Prepreg and carbon fiber reinforced composite materials

By using sizing agents with specific functions, the problems of poor compatibility and low adhesiveness in high-thermal resistance carbon fiber composites are solved, and good thermal stability and mechanical properties at high temperatures are achieved.

JP7671364B2Active Publication Date: 2025-05-01TORAY COMPOSITE MATERIALS AMERICA INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023558300
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-04
Filing Date
2021-12-02
Publication Date
2025-05-01
Estimated Expiration
2041-12-02

AI Technical Summary

Technical Problem

In the prior art, there are problems of poor compatibility and low adhesiveness between high heat-resistant sizing agents and high heat-resistant carbon fiber composites, resulting in a degradation of material properties when used at high temperatures.

Method used

A sizing agent with a specific function is used, which consists of a reaction component (A) that has two or more first functional groups that can react with high heat-resistant resins and have different second functional groups such as amides, ketones, esters, thiolenes, etc. This sizing agent achieves good compatibility and bonding between high heat-resistant carbon fiber composites.

Benefits of technology

It improves the thermal stability and mechanical properties of carbon fiber composites at high temperatures, especially the hardened interlayer shear strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671364000001
    Figure 0007671364000001
  • Figure 0007671364000002
    Figure 0007671364000002
  • Figure 0007671364000003
    Figure 0007671364000003
Patent Text Reader

Abstract

A prepreg is provided. The prepreg includes sizing-agent-coated carbon fibers and a thermosetting resin composition (B) impregnated between the sizing-agent-coated carbon fibers. The sizing agent includes a reactive component (A) having at least three reactive groups per molecule, which are (i) two or more first functional groups capable of reacting with the thermosetting resin composition (B) and (ii) at least one second functional group different from the two or more first functional groups (i). The second functional group includes at least one of amide, imide, urethane, urea, carbonyl, ester, sulfonyl, aromatic ring, or a combination thereof. The thermosetting resin composition (B) includes at least one thermosetting resin other than an epoxy resin, and has a glass transition temperature of 220° C. or higher after curing.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Application No. 63 / 121,628, entitled “PREPREG AND CARBON FIBER-REINFORCED COMPOSITE MATERIAL,” filed December 4, 2020, which is incorporated by reference herein.

[0002] The present invention relates to prepregs and fiber reinforced composites, such as carbon fiber reinforced composites. More specifically, the present disclosure provides prepregs having sizing agent coated carbon fibers well suited for use in fiber reinforced composites with high heat resistant thermosetting resin compositions suitable for aerospace and general industrial applications. [Background technology]

[0003] Fiber-reinforced composites (FRCs), which contain reinforcing fibers and matrix resins, are widely used as aircraft components, spacecraft components, automobile components, railroad vehicle components, ship components, sports equipment components, and computer components such as laptop computer housings, because they have excellent mechanical properties such as strength and rigidity, and are lightweight. FRC materials are manufactured by various methods, but the most widely used method is to use uncured matrix resin impregnated with reinforcing fibers as a prepreg. In this method, the prepregs are laminated and heated to form a composite material. The matrix resins used in prepregs include both thermoplastic resins and thermosetting resins. In many cases, thermosetting resins are superior in terms of ease of handling. When high performance is required in a higher temperature range or over a wider temperature range, bismaleimide (BMI) resins and benzoxazine (BOX) resins, which have excellent mechanical properties and can withstand high operating temperatures, are used in the matrix system.

[0004] The properties of FRC depend on the reinforcing fibers, the sizing agent on the reinforcing fibers, and the matrix resin. Important design properties include tensile strength modulus, compressive strength modulus, impact resistance, damage resistance, interlaminar shear strength, and toughness. In general, in FRC materials, the reinforcing fibers are responsible for most of these properties. However, the adhesion between the reinforcing fibers and the matrix resin affects physical properties such as interlaminar shear strength and toughness. This adhesion between the reinforcing fibers and the matrix is ​​influenced by the interaction between the sizing agent and the matrix. On the other hand, the matrix resin has the greatest effect on the compressive strength and transverse tensile properties. When FRC materials are used as structural materials, the interlaminar shear strength and compressive strength are particularly important properties. Therefore, if not only the matrix resin and the reinforcing fibers each have excellent properties individually, but also the adhesion between them is good, excellent properties can be obtained, which is generally improved by the use of sizing agents.

[0005] However, there is a problem associated with currently available sizing agents and high heat resistant matrix materials (those with a Tg of 220°C or greater) that they tend to be incompatible with one another. Another problem associated with currently available sizing agents is that they decompose at the elevated operating temperatures of parts containing high heat resistant resins. Additionally, there is another problem in that the sizing agents and the bonds formed between the sizing agents and the high heat resistant resins tend to degrade at the operating temperatures of the parts and at the temperatures required for curing the high heat resistant resins. This degradation and incompatibility problem manifests itself as reduced mechanical properties, such as reduced interlaminar shear strength of the cured composite.

[0006] Currently, as a method to solve the problem of poor compatibility and deterioration, there is a method of producing prepregs mainly using sizing agent-free (uncoated) carbon fibers in a high heat-resistant thermosetting resin matrix system such as BMI resin or BOX resin. By not including a sizing agent, it is possible to obtain a high thermal oxidative stability (TOS) of the carbon fiber without impairing the TOS of the high heat-resistant thermosetting resin matrix system. However, from the viewpoint of processability and quality, an increase in fluffing is observed in carbon fiber prepregs produced from uncoated fibers. This increase in fluffing is not only a processing problem but also tends to reduce the quality of the entire prepreg, which in turn directly leads to a decrease in mechanical properties, ease of handling, and ease of production. Attempts have been made to use a different sizing agent to solve this problem, but a deterioration in two important properties, TOS and / or adhesion, was observed. Traditionally, sizing agents that increase the TOS of both the carbon fiber and the cured carbon fiber-reinforced plastic (CFRP) made from the prepreg have reduced the overall adhesion of the carbon fiber to the high-temperature thermoset matrix system, either due to poor compatibility with the carbon fiber or poor compatibility with the high-temperature thermoset matrix system. This reduced adhesion is manifested as a loss of interlaminar shear strength. Also, attempts to increase the compatibility of the sizing agent with the high-temperature matrix system while maintaining good adhesion to the carbon fiber result in a loss of TOS, which reduces the overall service temperature of the CFRP produced from such prepregs. Yet another attempt is to use long-chain thermoplastic materials as high TOS sizing agents, which do not allow the use of environmentally friendly solvents such as water. Many of the high-temperature thermoset matrix systems are associated with very high costs, and these costs due to the reduced service temperature due to the reduced TOS of the carbon fiber with these sizing agents are not justified in the design of new aerospace parts.

[0007] The present invention takes the above into consideration and aims to provide a prepreg using sizing agent-coated carbon fibers well suited for use with (among other things) high heat resistant thermosetting resin compositions. These sizing agents also provide coated carbon fibers that are less likely to fluff or break when rubbed by guide rollers or advanced processing equipment during the manufacture of prepreg materials, and allow good adhesion to matrix resins such as BMI resins and BOX resins. Furthermore, these sizing agents maintain good TOS in the mechanical properties of composite products even when exposed to high temperatures. The effect of the sizing agent is seen as an improvement in the interlaminar shear strength of cured parts made from prepregs and carbon fibers containing the sizing agent. Summary of the Invention

[0008] In order to solve the above problems, the present inventors have discovered that by using a sizing-agent-coated carbon fiber in which a specific type of sizing agent is coated on a highly heat-resistant thermosetting resin composition, it is possible to reduce fiber fuzzing and breakage, thereby improving the quality of the prepreg, and to realize a carbon fiber reinforced composite material having good adhesion between the carbon fiber and the highly heat-resistant thermosetting resin composition and a high TOS.

[0009] The present invention provides a prepreg that comprises, consists of, or consists essentially of, a sizing-agent-coated carbon fiber and a high heat-resistant thermosetting resin composition (B) impregnated between the sizing-agent-coated carbon fiber. The sizing agent is composed of a reaction component (A) having (i) two or more first functional groups capable of reacting with the high heat-resistant thermosetting resin composition (B) and (ii) at least one second functional group different from the first functional group (i), the at least one second functional group being selected from the group consisting of amide, imide, urethane, urea, carbonyl, ester, sulfonyl, aromatic ring, or a combination thereof. The high heat-resistant thermosetting resin composition (B) is composed of at least one thermosetting resin other than an epoxy resin, and has a glass transition temperature of 220° C. or higher after curing. According to a particular embodiment, the (i) first functional group and (ii) the second functional group can be combined, especially in the case of an aromatic ring. For example, the epoxy group of the first functional group (i) may be bonded to an aromatic ring of the second functional group (ii).

[0010] In one aspect, there is provided a carbon fiber reinforced composite material obtained by curing a prepreg as disclosed above. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] All publications, patents, and patent applications cited herein are hereby incorporated by reference in their entirety for all purposes.

[0012] In this specification, the articles "a" and "an" are used to refer to one or more than one (i.e., at least one) of the grammatical object of the article. Incidentally, "a polymer resin" means one polymer resin or more than one polymer resin. All ranges cited herein are inclusive. As used throughout this specification, the terms "substantially" and "about" are used to express and imply small variations. For example, they can refer to weights or quantities that differ from the stated value by ±5% or less.

[0013] References throughout this specification to "one embodiment" or "an embodiment" mean that a particular feature, structure, or characteristic described in connection with an embodiment is included in at least one embodiment. Thus, the appearances of "in one embodiment" or "in an embodiment" in various places throughout this specification are not necessarily all referring to the same embodiment. Furthermore, particular features, structures, or characteristics may be combined in any suitable manner in one or more embodiments.

[0014] Unless otherwise specified, "room temperature" as used herein refers to a temperature of 25°C.

[0015] As used herein, the term PHR means "parts per hundred of resin" and refers only to the reactive portions of the resin formulation (i.e., the components of the resin formulation that undergo a chemical reaction when the resin formulation cures, e.g., bismaleimide and comonomer or benzoxazine and epoxy resin).

[0016] As used herein, the term "fiber reinforced composite material" is used interchangeably with the terms "fiber reinforced composite," "fiber reinforced polymer material," "fiber reinforced polymer," "fiber reinforced plastic material," "fiber reinforced plastic," and "carbon fiber reinforced polymer."

[0017] As used herein, the term "high temperature resistance" with respect to a prepreg or composite means a prepreg or composite that includes a thermosetting resin that has a glass transition temperature (Tg) of 220° C. or higher after curing, as measured according to the procedures set forth in the Examples described herein. The term "high temperature resistance" with respect to a thermosetting resin means a thermosetting resin that has a glass transition temperature (Tg) of 220° C. or higher after curing, as measured according to the procedures set forth in the Examples described herein.

[0018] The present invention relates to prepregs and fiber reinforced composites, such as carbon fiber reinforced composites. More specifically, the present disclosure provides prepregs including sizing-coated carbon fibers well suited for use in fiber reinforced composites with high heat resistant thermosetting resin compositions well suited for aerospace and general industrial applications.

[0019] According to the present disclosure, a prepreg using sizing agent-coated carbon fibers with excellent quality due to less fiber fuzzing and breakage can be obtained. Furthermore, by using the prepreg of the present disclosure, a carbon fiber reinforced composite material having good adhesion between the carbon fiber and the high heat resistance thermosetting resin matrix system can be obtained by curing the prepreg, which means that excellent thermal stability can be obtained. Such a fiber reinforced composite material exhibits excellent mechanical properties.

[0020] The prepreg and carbon fiber reinforced composite material of the present disclosure will be described in detail below.

[0021] The present inventors have conducted extensive research in light of the above problems, and have found that the above problems can be solved by using a prepreg containing a sizing agent-coated carbon fiber and a high heat-resistant thermosetting resin composition (B) impregnated between the sizing agent-coated carbon fiber in fiber-reinforced composite materials. The sizing agent comprises, consists of, or consists essentially of a reactive component (A) having (i) two or more first functional groups per molecule capable of reacting with the high heat-resistant thermosetting resin composition (B) and (ii) at least one second functional group per molecule containing at least one of amide, imide, urethane, urea, carbonyl, ester, sulfonyl, aromatic ring, or combinations thereof. The first (i) functional group and the second (ii) functional group are different from each other. The at least two first functional groups (i) may be the same or different from each other as long as they are different from the second functional group (ii). The highly heat-resistant thermosetting resin composition (B) contains at least one thermosetting resin other than an epoxy resin, and has a glass transition temperature of 220° C. or higher after curing.

[0022] Hereinafter, the embodiment of the prepreg according to the present invention and the carbon fiber reinforced composite material obtained by curing the prepreg will be described in more detail. The present invention is a prepreg containing a sizing-agent-coated carbon fiber and a high heat-resistant thermosetting resin. The sizing agent is composed of a reactive component (A) having (i) two or more first functional groups per molecule capable of reacting with a high heat-resistant thermosetting resin composition (B), and (ii) at least one group selected from the group consisting of amide, imide, urethane, urea, carbonyl, ester, sulfonyl, aromatic ring, or a combination thereof, and the high heat-resistant thermosetting resin is characterized in that the glass transition temperature after curing is 220°C or higher. First, a carbon fiber coated with a sizing agent composed of a reactive component (A) having (i) two or more first functional groups capable of reacting with a high heat-resistant thermosetting resin composition (B) and (ii) at least one second group containing at least one of amide, imide, urethane, urea, carbonyl, ester, sulfonyl, aromatic ring structure, or a combination thereof will be described. Reactant (A) The reactive component (A) used in the present invention is a compound having (i) two or more first functional groups per molecule capable of reacting with the high heat resistant thermosetting resin composition (B), and (ii) at least one second functional group in the molecule containing at least one of amide, imide, urethane, urea, carbonyl, ester, sulfonyl, aromatic ring, or a combination thereof.

[0023] Without being bound by any particular theory, when the number of first functional groups (i) per molecule is less than two, the number of functional groups capable of reacting with the highly heat-resistant thermosetting resin composition (B) is too small, and therefore the adhesive properties of the composite material obtained by curing the prepreg of the present invention may not be sufficiently improved.

[0024] In an embodiment of the present invention, reactive component (A) may be crosslinked to inhibit diffusion into the matrix resin.

[0025] In a particular embodiment of the present invention, the reactive component (A) has three or more first functional groups (i) in the molecule. The reactive component (A) may have three or more first functional groups (i), which can provide the advantage of improving adhesive properties such as interlaminar shear strength (ILSS).

[0026] Without being bound by theory, it is believed that at least one second functional group (ii) in the reactive component (A) molecule that includes at least one of amide, imide, urethane, urea, carbonyl, ester, sulfonyl, aromatic ring, or combinations thereof, provides good adhesion between the sizing agent and the carbon fibers. Examples of the first functional group (i) in the reactant (A) The first functional group (i) capable of reacting with the high heat resistant thermosetting resin composition (B) can be selected from those capable of participating in a free radical reaction, such as a vinyl group, an acryloyl group, a methacryloyl group, a halogen-containing group, an azo group, or a peroxide group.

[0027] In another embodiment, the first functional group (i) may be selected from a hydroxybenzyl group, a hydroxyphenoxy group, a phenoxy group, a phenolic hydroxyl group, an epoxy group, a carboxyl group, or an amino group.

[0028] In an embodiment, the first functional group (i) can be preferably selected from a vinyl group, an acryloyl group, a methacryloyl group, or an epoxy group from the viewpoints of stability and ease of handling when the sizing agent is coated on the carbon fiber surface, and of suitable reactivity with the highly heat-resistant thermosetting resin composition (B).

[0029] In another embodiment, reaction component (A) may contain one or more first functional groups (i). Component (A) having an epoxy group The reaction component (A) having an epoxy group as the first functional group (i) used in the present invention is not particularly limited or restricted as long as it has, in addition to the epoxy group, at least one second functional group (ii) containing at least one of amide, imide, urethane, urea, carbonyl, ester, sulfonyl, aromatic ring, or a combination thereof.

[0030] In an embodiment, an aromatic epoxy compound can be preferably used as the reaction component (A) having an aromatic ring structure. In this case, at least one of the two first functional groups (i) is an epoxy group, and the second functional group (ii) is an aromatic ring. In the present invention, the aromatic epoxy compound is preferably an epoxy compound having two or more types of first functional groups (i), in which the number of functional groups (i) is three or more, at least one of which is an epoxy group. The aromatic epoxy compound is more preferably an epoxy compound having two or more first functional groups (i). The number of first functional groups (i) may be four or more. The second functional group (ii) of the aromatic epoxy compound is preferably a functional group containing at least one of an amide group, an imide group, a urethane group, a urea group, and a sulfonyl group in addition to an aromatic ring. Without being bound by any particular theory, it is believed that in an aromatic epoxy compound having three or more epoxy groups in a molecule, or having an epoxy group and two or more other first functional groups (i), even if one epoxy group forms a covalent bond with an oxygen-containing functional group on the surface of a carbon fiber, the remaining two or more epoxy groups or other groups of the first functional group (i) can form a covalent bond or a hydrogen bond with the matrix resin. In this way, by being able to bond with both the carbon fiber and the matrix resin, the adhesiveness can be further improved. There is no particular limit to the upper limit of the number of first functional groups (i) containing epoxy groups, but a compound having 10 first functional groups (i) per molecule can provide sufficient adhesiveness.

[0031] In another embodiment, the aromatic epoxy compound preferably has an epoxy equivalent of less than 360 g / eq, more preferably less than 270 g / eq, and even more preferably less than 180 g / eq. Without being bound by a particular theory, an aromatic epoxy compound with an epoxy equivalent of less than 360 g / eq can form a high density covalent bond and further improve the adhesion between the carbon fiber and the matrix resin. Although the lower limit of the epoxy equivalent is not particularly limited, an aromatic epoxy compound with an epoxy equivalent of 90 g / eq or more can provide sufficient adhesion.

[0032] Examples of aliphatic epoxy compounds suitable as component (A) include, but are not limited to, glycidyl ether epoxy compounds obtained from aromatic polyols, glycidyl amine epoxy compounds obtained from aromatic amines having multiple active hydrogens, glycidyl ester epoxy compounds obtained from aromatic polycarboxylic acids, and epoxy compounds obtained by oxidizing aromatic compounds having multiple double bonds in the molecule.

[0033] Examples of glycidyl ether epoxy compounds include, but are not limited to, glycidyl ether epoxy compounds obtained by reacting a compound selected from bisphenol A, bisphenol F, bisphenol AD, bisphenol S, tetrabromobisphenol A, phenol novolac, cresol novolac, hydroquinone, resorcinol, 4,4'-dihydroxy-3,3',5,5'-tetramethylbiphenyl, 1,6-dihydroxynaphthalene, 9,9-bis(4-hydroxyphenyl)fluorene, tris(p-hydroxyphenyl)methane, and tetrakis(p-hydroxyphenyl)ethane with epichlorohydrin. In addition, examples of glycidyl ether epoxy compounds include glycidyl ether epoxy compounds having a biphenyl aralkyl skeleton.

[0034] Examples of the glycidyl amine epoxy compound include N,N-diglycidylaniline, N,N-diglycidyl-o-toluidine, and glycidyl ether epoxy compounds obtained by reacting epichlorohydrin with a compound selected from m-xylylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, and 9,9-bis(4-aminophenyl)fluorene.

[0035] Further, examples of the glycidylamine epoxy compound include epoxy compounds obtained by reacting epichlorohydrin with both the hydroxyl group and the amino group of aminophenol such as m-aminophenol, p-aminophenol, and 4-amino-3-methylphenol.

[0036] Examples of the glycidyl ester epoxy compound include glycidyl ester epoxy compounds obtained by reacting epichlorohydrin with phthalic acid, terephthalic acid, or hexahydrophthalic acid.

[0037] Examples of the aromatic epoxy compound used in the present invention include the above-exemplified epoxy compounds as well as epoxy compounds synthesized using the above-exemplified epoxy compounds as raw materials. An example of the epoxy compound is an epoxy compound synthesized by an oxazolidone ring formation reaction between bisphenol A diglycidyl ether and tolylene diisocyanate.

[0038] In a particular embodiment of the present invention, the aromatic epoxy compound preferably has, in addition to one or more epoxy groups (i), at least one or more second functional groups (ii) selected from amide groups, imide groups, urethane groups, urea groups, sulfonyl groups, carboxy groups, ester groups, sulfonyl groups, or combinations thereof.Non-limiting examples of such compounds include compounds having epoxy groups and amide groups, compounds having epoxy groups and imide groups, compounds having epoxy groups and urethane groups, compounds having epoxy groups and urea groups, and compounds having epoxy groups and sulfonyl groups.

[0039] Non-limiting examples of aromatic epoxy compounds having an amide group in addition to an epoxy group include glycidyl benzamide, amide-modified epoxy compounds, etc. The amide-modified epoxy can be obtained by reacting a carboxy group of a dicarboxylic acid amide containing an aromatic ring with an epoxy group of an epoxy compound having two or more epoxy groups.

[0040] An aromatic epoxy compound having a urethane group in addition to an epoxy group can be prepared by reacting a polyisocyanate having an aromatic ring with the terminal hydroxyl group of a polyethylene oxide monoalkyl ether in the same amount as the hydroxyl group, and reacting the isocyanate residue of the resulting reaction product with the hydroxyl group of the polyepoxy compound. Non-limiting examples of the polyisocyanate used here include 2,4-tolylene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, diphenylmethane diisocyanate, triphenylmethane triisocyanate, biphenyl-2,4,4'-triisocyanate, etc.

[0041] A non-limiting example of an aromatic epoxy compound having a urea group in addition to an epoxy group is a urea-modified epoxy compound, which can be prepared by reacting a carboxy group of a urea dicarboxylate with an epoxy group of an aromatic ring-containing epoxy compound having two or more epoxy groups.

[0042] A non-limiting example of an aromatic epoxy compound having a sulfonyl group in addition to an epoxy group is bisphenol S epoxy.

[0043] In the present invention, the aromatic epoxy compound is preferably any one of a phenol novolac type epoxy compound, a cresol novolac type epoxy compound, and tetraglycidyldiaminodiphenylmethane. These epoxy compounds have a large number of epoxy groups, a small epoxy equivalent, and two or more aromatic rings, and therefore improve the adhesion between the carbon fiber and the matrix resin, and also improve the mechanical properties such as the 0° tensile strength of the fiber reinforced composite material. The aromatic epoxy compound is more preferably a phenol novolac type epoxy compound or a cresol novolac type epoxy compound.

[0044] In the present invention, from the viewpoint of the stability and adhesiveness during long-term storage of the prepreg, the aromatic epoxy compound is preferably a phenol novolac type epoxy compound, a cresol novolac type epoxy compound, tetraglycidyldiaminodiphenylmethane, a bisphenol A type epoxy compound or a bisphenol F type epoxy compound, and more preferably a bisphenol A type epoxy compound or a bisphenol F type epoxy compound.

[0045] The sizing agent used in the present invention may further contain one or more additional components in addition to at least one of the aliphatic epoxy compounds and aromatic epoxy compounds. For example, if an adhesion promoter component that improves the adhesion between the carbon fiber and the sizing agent described herein, or a material that imparts bendability and flexibility to the carbon fiber coated with the sizing agent is included, the additional components may improve the ease of handling, abrasion resistance, and fluff resistance, and may improve the impregnation of the matrix resin into the carbon fiber. In the present invention, in order to improve the long-term stability of the prepreg, the sizing agent may further contain compounds other than the aliphatic epoxy compounds and aromatic epoxy compounds. The sizing agent may contain auxiliary components such as a dispersant and / or a surfactant to stabilize the sizing agent.

[0046] Without being bound by any theory, the epoxy compound used as the epoxy group-containing reactive component (A) is preferably selected from aromatic epoxy compounds, epoxy compounds having a hydantoin structure, epoxy compounds having an isocyanurate structure, and mixtures thereof, from the viewpoint of the heat resistance of the composite material obtained by curing the prepreg of the present invention. Component (A) containing a vinyl group, an acryloyl group, or a methacryloyl group There are no particular limitations or restrictions on the reaction component (A) used in the present invention, which has (i) a vinyl group, an acryloyl group and / or a methacryloyl group as a functional group.

[0047] For example, suitable compounds (A) may contain a functional group (i) selected from vinyl, acryloyl and methacryloyl groups as part of the monomer formed by the reaction of an unsaturated carboxylic acid with a polyol, an unsaturated carboxylic acid with a polyol, and a polymer of such a monomer. Examples of unsaturated alcohols that can be used here include olefin alcohols, which are reaction products of unsaturated carboxylic acids with polyols. Examples of olefin alcohols include allyl alcohol, crotyl alcohol, 3-buten-1-ol, 3-buten-2-ol, 3-penten-1-ol, 4-penten-1-ol, 4-penten-2-ol, 4-hexen-1-ol, 5-hexen-1-ol, and the like. In order to increase the number average molecular weight described later, olefin alcohols having an unsaturated group at the end are suitable. Examples of reaction products of unsaturated carboxylic acids and polyols include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl phthalate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, ethylene glycol mono(meth)acrylate, diethylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol polypropylene glycol mono(meth)acrylate, 1,6-hexanediol mono(meth)acrylate, neopentyl glycol mono(meth)acrylate, trimethylolpropane di(meth)acrylate, bisphenol A diglycidyl ether (meth)acrylic acid adduct, etc. As component (A), reaction products of unsaturated carboxylic acids and polyols can be preferably used.

[0048] Examples of the unsaturated carboxylic acid that can be used to form component (A) include acrylic acid, methacrylic acid, oleic acid, maleic acid, fumaric acid, and itaconic acid. Examples of the polyol that can be preferably used here include glycerol, ethylene glycol, diethylene glycol, polyethylene glycol, polypropylene glycol, polyalkylene glycol, arabitol, sorbitol, and 1,6-hexanemethylene diol.

[0049] Examples of the isocyanate compound as functional group (i) that can be used to form component (A) include tolylene diisocyanate, ditolylene diisocyanate, diphenylmethane diisocyanate, dimethyldiphenylmethane diisocyanate, hexamethylene diisocyanate, metaphenylene diisocyanate, propyl isocyanate, and butyl isocyanate.

[0050] The component (A) is formed by appropriately combining any one of the above unsaturated alcohols or unsaturated carboxylic acids with any one of the above isocyanate compounds, and appropriate reaction conditions are selected from known reaction conditions for forming urethane. After completion of the reaction, the reaction solvent is distilled off to easily obtain the target compound as component (A).

[0051] The reaction product, i.e., component (A), is preferably an unsaturated polyurethane compound having an acrylate group and a methacrylate group as the terminal unsaturated group (i), and at least one compound selected from phenyl glycidyl ether acrylate hexamethylene diisocyanate, phenyl glycidyl ether acrylate tolylene isocyanate, pentaerythritol acrylate hexamethylene diisocyanate, phenyl glycidyl ether triacrylate isophorone diisocyanate, glycerol dimethacrylate tolylene diisocyanate, glycerol dimethacrylate isophorone diisocyanate, pentaerythritol triacrylate tolylene diisocyanate, pentaerythritol triacrylate isophorone diisocyanate, and triallyl isocyanurate can be used.

[0052] When present, the number of unsaturated groups is preferably 2 or more per monomer in order to easily and uniformly increase the number average molecular weight on the carbon fiber surface to form a film and react with the high heat resistant thermosetting resin composition (B). 3 or more is more preferable. When a monomer having one unsaturated group at its end is heated and polymerized on the carbon fiber surface, the reaction with the high heat resistant thermosetting resin composition (B) does not proceed due to the small number of functional groups that can react with the high heat resistant thermosetting resin composition (B), and the adhesive properties of the composite material may not be improved. In order to ensure interaction with a specific amount of functional groups on the carbon fiber surface when forming a film on the carbon fiber surface, the polar group density as the number of polar groups per number average molecular weight of the monomer is 1×10 -3 The polar group density is preferably 3×10 or more / molecular weight. -3 More preferably, the number average molecular weight is 15×10 or more. -3 or less / number average molecular weight, preferably 7×10 -3 The molecular weight of the monomer is preferably 100 g / mol to 1500 g / mol, and the lower the viscosity, the easier it is to handle as a binder. A more preferred range is 500 g / mol to 1000 g / mol. Component (A) having a hydroxybenzyl group, a hydroxyphenoxy group, a phenoxy group, and a phenolic hydroxyl group There are no particular limitations or restrictions on the reactive component (A) having a hydroxybenzyl group, a hydroxyphenoxy group, a phenoxy group, and a phenolic hydroxyl group, and examples of the reactive component (A) that can be used include monomers selected from phenyl glycidyl ether acrylate, hexamethylene diisocyanate, phenyl glycidyl ether tolylene diisocyanate, and phenyl glycidyl ether isophorone diisocyanate, polymers obtained by polymerizing such monomers, and mixtures thereof. Component (A) containing an accelerator In an embodiment, the sizing agent used in the present invention may further include an accelerator for improving adhesion between the sizing agent-coated carbon fiber and the high heat-resistant thermosetting resin composition (B). Without being bound by a particular theory, the accelerator may promote covalent bond formation between the reactive component (A) and the oxygen-containing functional groups originally present on the surface of the carbon fiber, or between the epoxy compound (if used) and the oxygen-containing functional groups, such as carboxyl groups and hydroxyl groups, introduced by the oxidation treatment of the carbon fiber. The accelerator used in the present invention includes at least one compound that can be selected from tertiary amine compounds and / or tertiary amine salts having a molecular weight of 100 g / mol or more, quaternary ammonium salts having a cationic moiety represented by general formula (I) or general formula (II), and quaternary phosphonium salts and / or phosphine compounds.

[0053] [ka]

[0054] (wherein R1 to R4 are each C 1-22 The hydrocarbon group may have a hydroxyl group, and the CH2 group in the hydrocarbon group may be replaced by -O-, -O-CO- or -CO-O-.

[0055] [ka]

[0056] (where R5 is C 1-22 In the hydrocarbon group, the CH2 group may be replaced by -O-, -O-CO-, or -CO-O-; R6 and R7 are each a hydrogen atom or 1-8 wherein the CH2 group in the hydrocarbon group may be replaced by -O-, -O-CO-, or -CO-O-. In a specific embodiment of the present invention, the reaction component (A) used together with the accelerator can be preferably selected from compounds having two or more epoxy groups in the molecule and / or epoxy compounds having one or more epoxy groups in the molecule and at least one or more functional groups (ii) selected from amide groups, imide groups, urethane groups, urea groups, and sulfonyl groups. In another embodiment, the epoxy compound is preferably any one of phenol novolac type epoxy resins, cresol novolac type epoxy resins, and tetraglycidyldiaminodiphenylmethane. These epoxy resins have a large number of epoxy groups, a small epoxy equivalent, and two or more aromatic rings, and therefore improve the adhesion between carbon fibers and matrix resins and mechanical properties such as the 0° tensile strength of carbon fiber reinforced composite materials. The epoxy resin having two or more functional groups is more preferably a phenol novolac type epoxy resin or a cresol novolac type epoxy resin.

[0057] Specific examples of epoxy compounds having two or more epoxy groups include glycidyl ether type epoxy resins obtained from polyols, glycidyl amine type epoxy resins obtained from amines having multiple active hydrogens, glycidyl ester type epoxy resins obtained from polycarboxylic acids, and epoxy resins obtained by oxidizing compounds having multiple double bonds in the molecule.

[0058] Non-limiting examples of glycidyl ether type epoxy resins include glycidyl ether type epoxy resins obtained by reacting epichlorohydrin with bisphenol A, bisphenol F, bisphenol AD, bisphenol S, tetrabromobisphenol A, phenol novolac, cresol novolac, hydroquinone, resorcin, 4,4'-dihydroxy-3,3',5,5'-tetramethylbiphenyl, 1,6-dihydroxynaphthalene, 9,9-bis(4-hydroxyphenyl)fluorene, tris(p-hydroxyphenyl)methane, and tetrakis(p-hydroxyphenyl)ethane. Examples of glycidyl ether type epoxy resins include glycidyl ether type epoxy resins obtained by reacting epichlorohydrin with ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, tetrapropylene glycol, polypropylene glycol, trimethylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, polybutylene glycol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, hydrogenated bisphenol A, hydrogenated bisphenol F, glycerol, diglycerol, polyglycerol, trimethylolpropane, pentaerythritol, sorbitol, and arabitol. Additional examples of the glycidyl ether type epoxy resin include glycidyl ether epoxy resins having a dicyclopentadiene structure, and glycidyl ether epoxy resins having a biphenylaralkyl structure.

[0059] Non-limiting examples of glycidylamine type epoxy resins include N,N-diglycidylaniline, N,N-diglycidyl-o-toluidine, 1,3-bis(aminomethyl)cyclohexane, m-xylylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, and 9,9-bis(4-aminophenyl)fluorene, etc. Examples of glycidylamine type epoxy resins include epoxy resins obtained by reacting epichlorohydrin with both the hydroxyl group and the amino group of aminophenol such as m-aminophenol, p-aminophenol, and 4-amino-3-methylphenol, etc.

[0060] Non-limiting examples of the glycidyl ester type epoxy resin include glycidyl ester type epoxy resins obtained by reacting epichlorohydrin with phthalic acid, terephthalic acid, hexahydrophthalic acid, or dimer acid.

[0061] Non-limiting examples of epoxy resins as reaction component (A) obtained by oxidizing a compound having multiple double bonds in the molecule include epoxy resins having an epoxycyclohexane ring in the molecule, etc. Further examples of epoxy resins include epoxidized soybean oil, etc.

[0062] In addition to these epoxy resins, the epoxy compound used as the reactive component (A) in the present invention can be exemplified by epoxy resins such as triglycidyl isocyanurate. Further examples of the epoxy compound include epoxy resins synthesized using the epoxy resins exemplified above as raw materials, and epoxy resins synthesized by the oxazolidone ring formation reaction of bisphenol A diglycidyl ether and tolylene diisocyanate.

[0063] In the present invention, specific examples of the epoxy compound having one or more epoxy groups and at least one functional group selected from an amide group, an imide group, a urethane group, a urea group, and a sulfonyl group as the reaction component (A) include a compound having an epoxy group and an amide group, a compound having an epoxy group and an imide group, a compound having an epoxy group and a urethane group, a compound having an epoxy group and a urea group, and a compound having an epoxy group and a sulfonyl group.

[0064] Non-limiting examples of the reaction component (A) having an epoxy group and an amide group include glycidyl benzamide, amide-modified epoxy resins, etc. The amide-modified epoxy resins can be prepared by reacting the carboxy group of a dicarboxylic acid amide with the epoxy group of an epoxy resin having two or more epoxy groups.

[0065] A non-limiting example of the reactive component (A) having an epoxy group and an imide group is glycidyl phthalimide, etc. A specific example of this compound is "Denacol (registered trademark) EX-731" (manufactured by Nagase ChemteX Corporation).

[0066] Non-limiting examples of the reaction component (A) having an epoxy group and a urethane group include urethane-modified epoxy resins, specifically Adeka Resin (registered trademark) EPU-78-13S, EPU-6, EPU-11, EPU-15, EPU-16A, EPU-16N, EPU-17T-6, EPU-1348, EPU-1395 (manufactured by Adeka Corporation), etc. The compound can also be prepared by reacting a terminal hydroxyl group of a polyethylene oxide monoalkyl ether with a polyvalent isocyanate in the same amount as the terminal hydroxyl group, and reacting the isocyanate residue of the resulting reaction product with the hydroxyl group of a polyvalent epoxy resin. Other non-limiting examples of polyisocyanates useful as reactive component (A) herein include 2,4-tolylene diisocyanate, metaphenylene diisocyanate, paraphenylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, norbornane isocyanate, triphenylmethane triisocyanate, biphenyl-2,4,4'-triisocyanate, and the like.

[0067] Another example of the reactive component (A) having an epoxy group and a urea group is a urea-modified epoxy resin, which can be prepared by reacting the carboxy group of a urea dicarboxylate with the epoxy group of an epoxy resin having two or more epoxy groups.

[0068] An example of the reaction component (A) having an epoxy group and a sulfonyl group is bisphenol S type epoxy.

[0069] In certain embodiments of the present invention, the sizing agent used comprises at least one accelerator, preferably in an amount of 0.1 to 25 parts by weight per 100 parts by weight of reactive component (A). Carbon Fiber Examples of carbon fibers used in the present invention include polyacrylonitrile (PAN)-based carbon fibers, rayon-based carbon fibers, pitch-based carbon fibers, etc. Among these, PAN-based carbon fibers, which have an excellent balance between strength and elastic modulus, are preferably used.

[0070] In a particular embodiment of the present invention, the carbon fibers are in the form of carbon fiber bundles having a strand strength of preferably 3.5 GPa or more, more preferably 4.0 GPa or more, and particularly preferably 5.0 GPa or more. The resulting carbon fiber bundles have a strand modulus of preferably 220 GPa or more, more preferably 240 GPa or more, and particularly preferably 280 GPa or more.

[0071] In the present invention, the strand tensile strength and modulus of elasticity of the carbon fiber bundle can be measured by the following procedure according to the resin impregnated strand test method described in JIS-R-7608 (2004). The resin blend is "Celloxide (registered trademark)" 2021P (manufactured by Daicel Chemical Industries, Ltd.) / boron trifluoride monoethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) / acetone = 100 / 3 / 4 (parts by mass), and the curing conditions are normal pressure, 130 ° C, and 30 minutes. Ten strands of the carbon fiber bundle are tested, and the average values ​​are calculated as the strand tensile strength and strand modulus of elasticity.

[0072] In a specific embodiment of the present invention, the carbon fiber preferably has a surface roughness (Ra) of 6.0 to 100 nm. The surface roughness (Ra) is more preferably 15 to 80 nm, and particularly preferably 30 to 60 nm. Carbon fibers with a surface roughness (Ra) of 6.0 to 60 nm have a highly active surface at the edge, and therefore, without being bound by a specific theory, can enhance the reactivity with the epoxy group and other functional groups of the reactive component (A) of the sizing agent. Again, without being bound by theory, such carbon fibers are preferred because the roughness can improve the interfacial adhesion. Carbon fibers with a surface roughness (Ra) of 6.0 to 100 nm have an uneven surface, and the interfacial adhesion can be improved by the anchor effect of the sizing agent. Therefore, such rough carbon fibers are preferred.

[0073] The average roughness (Ra) of the carbon fiber surface can be measured using an atomic force microscope (AFM). For example, the carbon fibers are cut into lengths of several millimeters, fixed to a substrate (silicon wafer) with silver paste, and a three-dimensional surface shape image of the center of each single fiber is observed using an atomic force microscope. An example of an atomic force microscope that can be used is the NanoScope IIIa equipped with the Dimension 3000 stage system manufactured by Digital Instruments, which can perform observations under the following observation conditions, in scan mode and tapping mode. Probe Silicon Cantilever Scan area: 0.6μm×0.6μm Scan speed: 0.3Hz Resolution: 512 x 512 Measurement environment: Atmospheric, room temperature For each sample, an image is obtained by observing one area on each individual fiber, and the fiber cross-section curve is approximated by a three-dimensional curved surface. The average roughness (Re) is calculated from the entire image obtained. It is preferable to obtain the average roughness (Ra) of five single fibers and evaluate the average value.

[0074] In a specific embodiment of the present invention, the carbon fibers preferably have a total fineness of 400 to 3000 tex. The carbon fibers preferably have a filament count of 1000 to 100000, more preferably 3000 to 50000.

[0075] In a specific embodiment of the present invention, the carbon fiber preferably has a single fiber diameter of 4.5 to 7.5 μm. When the single fiber diameter is 7.5 μm or less, the carbon fiber can have high strength and high elastic modulus, which is preferable. The single fiber diameter is more preferably 6 μm or less, and particularly preferably 5.5 μm or less. When the single fiber diameter is 4.5 μm or more, the carbon fiber is less likely to break and the productivity is less likely to decrease, which is preferable.

[0076] In a specific embodiment of the present invention, the carbon fiber has a surface oxygen concentration (O / C) in the range of preferably 0.05 to 0.50, more preferably 0.07 to 0.40, particularly preferably 0.09 to 0.30, and more particularly preferably 0.12 to 0.25. Here, the surface oxygen concentration (O / C) is the ratio of the number of oxygen (O) atoms to the number of carbon (C) atoms on the surface of the fiber, and is determined by X-ray photoelectron spectroscopy. If the surface oxygen concentration (O / C) is 0.05 or more, oxygen-containing functional groups are maintained on the surface of the carbon fiber, so that strong adhesion with the matrix resin can be realized. If the surface oxygen concentration (O / C) is 0.5 or less, the decrease in strength of the carbon fiber itself due to oxidation of the carbon fiber can be suppressed.

[0077] The surface oxygen concentration of carbon fibers is measured by X-ray photoelectron spectroscopy in the following procedure. First, the dust and other substances adhering to the surface of the carbon fibers are removed using a solvent, and then the carbon fibers are cut into 20 mm pieces and spread out and placed on a copper sample holder. The measurement is performed using an AIKα 1,2 The X-ray source is 1.33 ×10 -6 Pa The photoelectron takeoff angle is adjusted to 90°. The peak correction value for the charge during measurement is C 1s The binding energy value of the main peak (peak top) of is set to 284.6 eV, and a straight baseline is drawn in the range of 282 to 296 eV. 1s Calculate the peak area. 1s The peak area is calculated by drawing a straight baseline in the range of 528 to 540 eV. The surface oxygen concentration (O / C) is calculated by 1s The atomic ratio is calculated by dividing the peak area ratio by the sensitivity correction value specific to the device. For the ESCA-1600 manufactured by Ulvac-Phi, the sensitivity correction value specific to the device is 2.33. Carbon fiber manufacturing method Next, a method for producing the PAN-based carbon fiber will be described.

[0078] Examples of spinning methods that can be used to prepare precursor fibers of carbon fibers include dry spinning, wet spinning, and dry-wet spinning. In order to easily produce high-strength carbon fibers, wet spinning or dry-wet spinning is preferably used. In particular, dry-wet spinning is more preferably used because it can produce carbon fibers with high strength.

[0079] As described above, in order to further improve the adhesion between the carbon fiber and the matrix resin, the carbon fiber preferably has a surface roughness (Ra) of 6.0 to 100 nm, and in order to prepare carbon fiber having such a surface roughness, it is preferable to employ wet spinning for spinning the precursor fiber.

[0080] The spinning solution used may be a solution in which a homopolymer or copolymer of polyacrylonitrile is dissolved in a solvent. Examples of the solvent include organic solvents such as dimethylsulfoxide, dimethylformamide, and dimethylacetamide, and aqueous solutions of inorganic compounds such as nitric acid, sodium rhodanate, zinc chloride, and sodium thiocyanate. Preferred solvents are dimethylsulfoxide and dimethylacetamide.

[0081] The spinning solution is spun through a spinneret, discharged into a spinning bath or air, and solidified in the spinning bath. The spinning bath used may be an aqueous solution of the same solvent as that used in the spinning solution. The spinning solution preferably contains the same solvent as that used in the spinning solution, and an aqueous dimethylsulfoxide solution or an aqueous dimethylacetamide solution is preferred. The fibers solidified in the spinning bath are washed with water and stretched to obtain precursor fibers. The obtained precursor fibers are subjected to flame retardant treatment and carbonization treatment, and further to graphite treatment as desired to obtain carbon fibers. The carbonization and graphite treatments are preferably performed under conditions where the maximum heat treatment temperature is 1100°C or higher, more preferably 1400 to 3000°C.

[0082] In order to improve the adhesion to the matrix resin, the obtained carbon fiber is usually subjected to an oxidation treatment to introduce an oxygen-containing functional group. The oxidation treatment method may be gas phase oxidation, liquid phase oxidation, or liquid phase electrolytic oxidation, and it is preferable to adopt liquid phase electrolytic oxidation from the viewpoint of high productivity and uniform treatment.

[0083] In a specific embodiment of the present invention, the electrolyte used in the liquid-phase electrolytic oxidation is exemplified by an acid electrolyte and an alkaline electrolyte. From the viewpoint of adhesion, it is more preferable to coat the carbon fiber with a sizing agent after the liquid-phase electrolytic oxidation in an alkaline electrolyte.

[0084] Examples of acid electrolytes include inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, boric acid, and carbonic acid, organic acids such as acetic acid, butyric acid, oxalic acid, acrylic acid, and maleic acid, and salts such as ammonium sulfate and ammonium hydrogen sulfate. Among these, sulfuric acid and nitric acid, which show strong acidity, are preferably used.

[0085] Specific examples of alkaline electrolytes include aqueous solutions of hydroxides such as sodium hydroxide, potassium hydroxide, magnesium hydroxide, calcium hydroxide, and barium hydroxide; aqueous solutions of carbonates such as sodium carbonate, potassium carbonate, magnesium carbonate, calcium carbonate, barium carbonate, and ammonium carbonate; aqueous solutions of bicarbonates such as sodium bicarbonate, potassium bicarbonate, magnesium bicarbonate, calcium bicarbonate, barium bicarbonate, and ammonium bicarbonate; aqueous solutions of ammonia, tetraalkylammonium hydroxide, and hydrazine. Among these, aqueous solutions of ammonium carbonate and ammonium bicarbonate are preferably used as the electrolyte because they do not contain an alkali metal that inhibits the curing of the matrix resin, or an aqueous solution of tetraalkylammonium hydroxide that exhibits strong alkalinity is preferably used.

[0086] In a specific embodiment of the present invention, the concentration of the electrolyte is preferably in the range of 0.01 to 5 mol / L, more preferably 0.1 to 1 mol / L. If the concentration of the electrolyte is 0.01 mol / L or more, the electrolysis can be performed at a lower voltage, which is advantageous in terms of operation costs. If the concentration of the electrolyte is 5 mol / L or less, it is advantageous in terms of safety.

[0087] In a specific embodiment of the present invention, the temperature of the electrolytic solution is preferably 10 to 100° C., more preferably 10 to 40° C. An electrolytic solution temperature of 10° C. or higher improves the efficiency of the electrolytic treatment and is advantageous in terms of operation costs. An electrolytic solution temperature of less than 100° C. is advantageous in terms of safety.

[0088] In a particular embodiment of the present invention, the amount of electricity during liquid-phase electrolytic oxidation is preferably optimized according to the degree of carbonization of the carbon fiber, with a larger amount of electricity being required to treat carbon fiber having a high elastic modulus.

[0089] In a specific embodiment of the present invention, the current density during the liquid-phase electrolytic oxidation is 1 m of the surface area of ​​the carbon fiber in the electrolytic treatment solution. 2 Preferably, 1.5 to 1000 A / m 2 , more preferably 3 to 500 A / m 2 The current density is 1.5A / m 2 If the current density is 1000A / m or more, the efficiency of the electrolytic treatment is improved, which is advantageous in terms of operating costs. 2 The following is advantageous in terms of safety.

[0090] In a specific embodiment of the present invention, the carbon fiber after electrolytic treatment is preferably washed with water and dried. The washing method may be, for example, immersion or spraying. Among them, immersion is preferably adopted from the viewpoint of easy washing, and immersion is preferably performed while vibrating the carbon fiber with ultrasonic waves. If the drying temperature is too high, the functional group on the outermost surface of the carbon fiber is easily thermally decomposed, and the functional group is decomposed. Therefore, drying is preferably performed at a temperature as low as possible. Specifically, the drying temperature is preferably 250°C or less, more preferably 210°C or less. In consideration of drying efficiency, the drying temperature is preferably 110°C or more, more preferably 140°C or more. Manufacturing method of sizing agent-coated carbon fiber Next, a sizing-agent-coated carbon fiber obtained by applying a sizing agent to carbon fiber to coat it will be described. The sizing agent used in the present invention is composed of a reactive component (A) having two or more functional groups (i) capable of reacting with a high heat-resistant thermosetting resin composition (B) and at least one functional group (ii) containing at least one of amide, imide, urethane, urea, carbonyl, ester, sulfonyl, and aromatic ring structures, or combinations thereof, and may further contain additional components.

[0091] In a specific embodiment of the present invention, the method of coating carbon fibers with a sizing agent is preferably a single-coating method using a sizing agent-containing liquid in which at least one of the reaction components (A) and other components are simultaneously dissolved or dispersed in a solvent, or a multi-coating method using a sizing agent-containing liquid in which either the reaction component (A) or other components is selected and dissolved or dispersed in a corresponding solvent. In the present invention, from the viewpoint of effect and ease of processing, a one-step coating method in which the carbon fibers are coated at once with a sizing agent-containing liquid containing all the components of the sizing agent is more preferably adopted.

[0092] The sizing agent of the present invention can be used as a sizing agent-containing liquid prepared by diluting the sizing agent components with a solvent. Examples of the solvent include water, methanol, ethanol, isopropanol, acetone, methyl ethyl ketone, dimethylformamide, and dimethylacetamide. Specifically, from the viewpoints of ease of handling and safety, an aqueous emulsion emulsified with a surfactant or an aqueous solution is preferably used.

[0093] In a specific embodiment of the present invention, the nonionic surfactant may be a combination of one or more selected from ether-type surfactants such as polyoxyethylene alkyl ethers, short-chain polyoxyethylene alkyl ethers, polyoxyethylene secondary alcohol ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene sterol ethers, polyoxyethylene lanolin derivatives, ethylene oxide derivatives of alkylphenol-formaldehyde condensates, polyoxyethylene polyoxypropylene block copolymers, and polyoxyethylene polyoxypropylene alkyl ethers; ether-ester-type surfactants such as polyoxyethylene glycol fatty acid esters, polyoxyethylene castor oil, hydrogenated castor oil, polyoxyethylene sorbitan fatty acid esters, and polyoxyethylene sorbitol fatty acid esters; and ester-type surfactants such as polyethylene glycol fatty acid esters and polyglycerin fatty acid esters. The nonionic surfactant preferably used is a phenol adduct (block or random adduct in the case of two or more alkylene oxide adducts) of an alkylene oxide (e.g., ethylene oxide, propylene oxide, or butylene oxide), and the phenol is a monocyclic phenol (phenol having one aromatic ring) such as phenol, a phenol having one or more alkyl groups, and a polyhydric phenol and a polycyclic phenol (phenol having two or more aromatic rings) such as phenylphenol, cumylphenol, benzylphenol, hydroquinone monophenyl ether, naphthol, bisphenol, etc., a reaction product (styrenated phenol) of a monocyclic phenol or a polycyclic phenol, etc. with a styrene (styrene or α-methylstyrene, etc.). Among them, an ethylene oxide adduct or a propylene oxide adduct of a styrenated phenol can be preferably used. The method of adding an alkylene oxide to such a phenol may be any ordinary method. The number of moles of addition is preferably 1 to 120. A more preferable range is 10 to 90, and a particularly preferable range is 30 to 80.

[0094] In order to further stabilize the emulsion, in addition to nonionic surfactants, anionic surfactants such as carboxylates, sulfonates, sulfates, and phosphates, cationic surfactants such as aliphatic amine salts and fatty acid quaternary ammonium salts, and amphoteric surfactants such as carboxybetaine and aminocarboxylic acids can also be used.

[0095] The sizing-agent-containing liquid usually contains the sizing agent at a concentration in the range of 0.2% by mass to 20% by mass.

[0096] Examples of the method of applying a sizing agent to carbon fibers (method of coating carbon fibers with a sizing agent) include a method of immersing carbon fibers in a sizing agent-containing liquid via a roller, a method of contacting carbon fibers with a roller to which a sizing agent-containing liquid is attached, and a method of spraying the sizing agent-containing liquid onto carbon fibers. The method of applying the sizing agent may be a batch method or a continuous method, and the continuous method is preferably adopted because it has good productivity and small variation. During application, it is preferable to control conditions such as the concentration and temperature of the sizing agent-containing liquid and the thread tension in order to apply an appropriate amount of the active ingredient in the sizing agent uniformly onto the carbon fibers. When applying the sizing agent, it is preferable to vibrate the carbon fibers with ultrasonic waves.

[0097] In order to suppress a change in the concentration of the sizing agent due to evaporation of the solvent when coating the carbon fibers with the sizing liquid, the sizing-agent-containing liquid preferably has a liquid temperature in the range of 10 to 50° C. Furthermore, by adjusting a throttle for extracting excess sizing-agent-containing liquid after application of the sizing-agent-containing liquid, the amount of sizing agent attached can be controlled and the sizing agent can be uniformly permeated into the carbon fibers.

[0098] After being coated with the sizing agent, the carbon fibers are preferably heated at a temperature in the range of 160 to 260 ° C for 30 to 600 seconds. The heat treatment conditions are more preferably 170 to 250 ° C for 30 to 500 seconds, and particularly preferably 180 to 240 ° C for 30 to 300 seconds. Without being bound by a particular theory, heat treatment under conditions of less than 160 ° C and / or less than 30 seconds cannot promote the interaction between the reaction component (A) that may contain an aliphatic epoxy compound in the sizing agent and the oxygen-containing functional group on the carbon fiber surface, and as a result, the adhesion between the carbon fibers and the matrix resin may be insufficient. Alternatively, or in addition, at this low temperature, the carbon fibers may not be dried sufficiently or the solvent may not be removed sufficiently. Heat treatment at temperatures above 260° C. and / or for times greater than 600 seconds may cause decomposition and volatilization of the sizing agent, and therefore, without being bound to a particular theory, these high temperatures may not be able to promote interaction with the carbon fibers, resulting in poor adhesion between the carbon fibers and the matrix resin.

[0099] The heat treatment can be carried out by microwave irradiation and / or infrared irradiation. When the sizing-agent-coated carbon fibers are heat-treated by microwave irradiation and / or infrared irradiation, the microwaves penetrate the carbon fibers and are absorbed by the carbon fibers, so that the carbon fibers, which are the objects to be heated, can be heated to the desired temperature in a short time. Microwave irradiation and / or infrared irradiation can rapidly heat the inside of the carbon fibers. This can reduce the temperature difference between the inside and outside of the carbon fiber bundle, and can reduce uneven adhesion of the sizing agent.

[0100] In the present invention, the amount of the sizing agent on the carbon fiber is preferably 0.1 to 10.0% by mass, more preferably 0.2 to 3.0% by mass, based on the sizing-agent-coated carbon fiber. When the sizing agent is coated at 0.1% by mass or more, the sizing-agent-coated carbon fiber can withstand friction with a metal guide through which the carbon fiber passes during prepreg production or weaving, and the generation of fluff is suppressed, so that a carbon fiber sheet with excellent quality such as smoothness can be produced. When the amount of the sizing agent attached is 10.0% by mass or less, the matrix resin can be infiltrated into the carbon fiber without being hindered by the coating of the sizing agent around the carbon fiber coated with the sizing agent. As a result, no voids are generated in the target composite material, and therefore the composite material has excellent quality and excellent mechanical properties.

[0101] The amount of sizing agent attached is determined by weighing out approximately 2±0.5 g of sizing-agent-coated carbon fiber, heat-treating the carbon fiber at 450°C for 15 minutes in a nitrogen atmosphere, determining the change in mass before and after heat treatment, and dividing the change in mass by the mass before heat treatment (mass %).

[0102] In a specific embodiment of the present invention, the sizing agent layer applied to the carbon fiber and dried preferably has a thickness in the range of 2.0 to 20 nm and a maximum thickness less than twice the minimum thickness. The sizing agent layer having such a uniform thickness can stably obtain a large adhesion improvement effect and stably obtain excellent high-order processability. Covering Method In one embodiment, even when the reactive component (A) contains a polymerizable compound (i.e., is a monomer), the carbon fiber coated with the reactive component (A) having a functional group (i) capable of reacting with the high heat-resistant thermosetting resin composition (B) can be heated to polymerize the monomer to obtain the sizing-agent-coated carbon fiber of the present invention. Specifically, the carbon fiber bundle can be coated with the monomer, and then the carbon fiber bundle is pre-dried with a heating roller. Furthermore, the main drying is performed using a hot air dryer, and the monomer is thermally polymerized. After the carbon fiber bundle is coated with the monomer, the fiber bundle can be stretched and fixed at the same time by pre-drying with a heating roller. Furthermore, it is preferable to perform the main drying and the thermal polymerization at the same time because the flexibility of the obtained carbon fiber bundle can be maintained. If the flexibility can be ensured, the pre-drying may be omitted.

[0103] The sizing-agent-coated carbon fiber of the present invention is used in the form of, for example, a tow, a woven fabric, a knit, a braid, a woven fabric, a mat, a chopped strand, etc. In particular, for applications requiring high specific strength and specific elastic modulus, a tow prepared by arranging carbon fibers in one direction is most preferable, and a prepreg prepared by further impregnating the tow with the highly heat-resistant thermosetting resin composition (B) is preferably used. High heat resistant thermosetting resin composition (B) The high heat resistance thermosetting resin composition (B) used in the present invention is composed of at least one thermosetting resin other than epoxy resin. The type of thermosetting resin other than epoxy resin used in the present invention is not particularly limited or restricted as long as it can undergo a crosslinking reaction by heat and at least partially form a three-dimensional crosslinked structure. Examples of such thermosetting resins include unsaturated polyester compounds, vinyl ester compounds, bismaleimide compounds, benzoxazine compounds, phenol compounds, urea compounds, melamine compounds, and thermosetting polyimide compounds, as well as modified compounds thereof and blends of two or more of these. The term "high heat resistance" as used herein means a resin that has a glass transition temperature of 220°C or higher when cured.

[0104] Cured resin Tg The high heat resistance thermosetting resin composition (B) has a glass transition temperature (Tg) of 220° C. or higher after curing. In another embodiment, Tg is preferably 240° C. or higher, more preferably 260° C. or higher. Tg can be measured by the G' onset method (described in more detail in the Examples) using a dynamic viscoelasticity measuring device (ARES, manufactured by TA Instruments). If Tg is 220° C. or higher, the sizing-agent-coated carbon fiber reinforced composite material produced from the prepreg of the present invention exhibits high thermal performance at higher temperatures.

[0105] In a specific embodiment, the curing profile is not particularly limited as long as it does not impair the effects of the present invention. If a higher Tg is desired, the high heat resistance thermosetting resin composition (B) can be cured at a higher temperature. Bismaleimide resin composition The bismaleimide resin composition according to the present invention may include a bismaleimide compound (B-1), a comonomer (C), a thermoplastic toughening agent, and a resin stabilizer. The combination of bismaleimide compounds (B-1) is preferably, but not necessarily, a eutectic mixture. A eutectic mixture is one in which the melting point of the mixture is at least lower than the melting point of each individual bismaleimide compound (B-1). In a eutectic mixture, several types of bismaleimide compounds (B-1) may be present. In one embodiment, the number of bismaleimide compounds (B-1) is three. The combination of bismaleimide compounds (B-1) is selected to provide an amorphous prepreg matrix resin after curing. By "amorphous" it is meant that the crystallinity of the bismaleimide resin composition is less than 5%. The bismaleimide resin composition is preferably at least 97% amorphous (i.e., not more than 3% crystalline). More preferably, the mixture is at least 99% amorphous (i.e., not more than 1% crystalline). The degree of crystallization of a resin is determined by conventional measurements such as differential scanning calorimetry, which are well known in the art. Bismaleimide compound (B-1) The bismaleimide compound (B-1) used in the present invention includes any of the known bismaleimide compounds. The bismaleimide compound (B-1) is typically prepared by reacting maleic anhydride or substituted maleic anhydride with aromatic and / or aliphatic diamines. Exemplary bismaleimides include N,N'-4,4'-diphenylmethane-bismaleimide, N,N'-2,4-toluene-bismaleimide, N,N'-2,6-toluene-bismaleimide, N,N'-2,2,4-trimethylhexane-bismaleimide, N,N'-ethylene-bis-maleimide, N,N'-ethylene-bis(2-methyl)maleimide, N,N'-trimethylene-bis-maleimide, N,N'-tetramethylene-bis-maleimide, N,N'-hexamethylene-bis Maleimide, N,N'-1,4-cyclohexylene-bismaleimide, N,N'-meta-phenylene-bismaleimide, N,N'-para-phenylene-bismaleimide, N,N'-4,4'-3,3'-dichlorodiphenylmethane-bismaleimide, N,N'-4,4'-diphenylether-bismaleimide, N,N'-4,4'-diphenylsulfone-bismaleimide, N,N'-4,4'-dicyclohexylmethane-bismaleimide, N,N'-α,α'-4,4'-dimethylene Cyclohexane-bismaleimide, N,N'-meta-xylene-bismaleimide, N,N'-para-xylene-bismaleimide, N,N'-4,4'-diphenylcyclohexane-bismaleimide, N,N'-meta-phenyl-bistetrahydrophthalimide, N,N'-4,4'-diphenylmethane-biscitraconimide, N,N'-4,4'-2,2-diphenylpropane-bismaleimide, N,N'-4,4-1,1-diphenylpropane-bismaleimide, N,N'-4,4'-triphenyl Nylmethane-bismaleimide, N,N'-α,α-1,3-dipropylene-5,5-dimethylhydantoin-bismaleimide, N,N'-4,4'-(1,1,1-triphenylethane)-bis-maleimide, N,N'-3,5-triazole-1,2,4-bis-maleimide, N,N'-4,4'-diphenylmethane-bis-itaconimide, N,N'-paraphenylene-bis-itaconimide, N,N'-4,4'-diphenylmethane-bis-dimethyl-maleimide, N,N'-4,4'-2,2-diphenylpropane-bisdimethyl-maleimide;N,N'-hexamethylene-bisdimethyl-maleimide;N,N'-4,4'-(diphenylether)-bisdimethyl-maleimide;N,N'-4,4'-diphenylsulfone-bisdimethylmaleimide;N,N'-(oxydiparaphenylene)-bis-maleimide;N,N'-(oxydiparaphenylene)-bis-(2-methylmaleimide);N,N'-(methylenediparaphenylene)-bis-maleimide;N,N'-(methylenediparaphenylene)-bis-(2-methylmaleimide);N,N'-(methylenediparaphenylene)-bis-(2-phenylmaleimide);N,N'-(sulfonyldiparaphenylene)-bismaleimide;N,N'-( thiodiparaphenylene)-bismaleimide, N,N'-(dithiodiparaphenylene)-bismaleimide, N,N'-(sulfonyldimethaphenylene)-bismaleimide, N,N'-(ortho,paraisopropylidenediphenylene)-bismaleimide, N,N'-(isopropylidenediparaphenylene)-bismaleimide, N,N'-(ortho,paracyclohexylidene diphenylene)-bismaleimide, N,N'-(cyclohexylidene diparaphenylene)-bismaleimide, N,N'-(ethylene-para-phenylene)-bismaleimide, N,N'-(4,4''-para-triphenylene)-bis-maleimide, N,N'-(para-phenylenedioxy-para-phenylene)-bis-maleimide, N,N'-(methylene di-para-phenylene)-bis-(2,3-dichloromaleimide), N,N'-(oxy-para-phenylene)-bis-(2-chloromaleimide), and mixtures thereof.

[0106] The specific combination of three or more bismaleimide compounds used to make the bismaleimide resin composition may vary widely, provided that it provides an amorphous, preferably eutectic, mixture after addition of comonomer (C), (optional) thermoplastic toughener, and (optional) resin distribution stabilizer, that has the flexibility, tack, and cure properties necessary for use as a prepreg resin.

[0107] Suitable mixtures of three or more bismaleimides are commercially available. For example, Compimide® 353A is a mixture of N,N'-4,4'-diphenylmethane-bismaleimide, N,N'-2,4-toluene-bismaleimide, and N,N'-2,2,4-trimethylhexane-bismaleimide available from Evonik Industries AG. Compimide® 353A is a preferred eutectic mixture of bismaleimide monomers. Comonomer (C) The comonomer (C) used in the present invention includes any of the comonomers that are usually combined with bismaleimides. Comonomers include, for example, diamines, polyamines, and alkenyl aromatic compounds such as alkenyl phenols and alkenyl phenoxy ethers. Preferred comonomers are alkenyl phenols, such as allyl, methallyl, and propenyl phenols. Specific examples include o,o'-diallyl bisphenol A, eugenol, eugenol methyl ether, and similar compounds, as disclosed in U.S. Pat. No. 4,100,140, ​​the contents of which are incorporated herein for all purposes. Particularly preferred comonomers are o,o'-diallyl bisphenol A and o,o'-dipropenyl bisphenol A. Compimide® TM124 is a commercially available co-curing agent available from Evonik Industries AG, and includes o,o'-diallyl bisphenol A.

[0108] In one embodiment, the comonomer (C) has at least one vinyl group and at least one group selected from a hydroxyl group and a thiol group. Without being bound by theory, it is believed that the comonomer (C) having at least one vinyl group and at least one group selected from a hydroxyl group and a thiol group improves the adhesion of the ILSS, etc.

[0109] In another embodiment of the present invention, the molar ratio of the comonomer (C) to the bismaleimide compound (B-1) defined by [(C) / (B-1)] can be 0.2 to 0.8. In one embodiment, the lower limit of the molar ratio (C) / (B-1) is 0.2 or more, 0.21 or more, 0.22 or more, 0.23 or more, 0.24 or more, 0.25 or more, 0.26 or more, 0.27 or more, 0.28 or more, 0.29 or more, or 0.3 or more. Furthermore, the upper limit of the molar ratio of [C] / [B-1] is 0.80 or less, 0.79 or less, 0.78 or less, 0.77 or less, 0.76 or less, 0.75 or less, 0.74 or less, 0.73 or less, 0.72 or less, 0.71 or less, 0.70 or less, 0.69 or less, 0.68 or less, 0.67 or less, 0.66 or less, 0.65 or less, 0.64 or less, 0.63 or less. or less, 0.62 or less, 0.61 or less, 0.60 or less, 0.59 or less, 0.58 or less, 0.57 or less, 0.56 or less, 0.55 or less, 0.54 or less, 0.53 or less, 0.52 or less, 0.51 or less, 0.50 or less, 0.49 or less, 0.48 or less, 0.47 or less, 0.46 or less, 0.45 or less, 0.44 or less, or 0.43 or less. Within this range, the bismaleimide resin composition has a Tg of 220° C. or more.

[0110] In another embodiment of the present invention, the molar ratio of the comonomer (C) to the bismaleimide compound (B-1), [(C) / (B-1)], is 0.45 or less from the viewpoint of improving the adhesiveness of ILSS, etc. In one embodiment, the molar ratio is 0.44 or less, 0.43 or less, 0.42 or less, 0.41 or less, 0.40 or less, 0.39 or less, 0.38 or less, 37 or less, 0.36 or less, 0.35 or less, 0.34 or less, 0.33 or less, 0.32 or less, 0.31 or less, 0.30 or less, 0.29 or less, 0.28 or less, 27 or less, 0.26 or less, 0.25 or less, 0.24 or less, 0.23 or less, 0.22 or less, or 0.21 or less.

[0111] In another embodiment of the present invention, the molar ratio of the comonomer (C) to the bismaleimide compound (B-1) defined by (C) / (B-1) is greater than 0.20 from the viewpoint of improving adhesion such as Tg and ILSS TOS. In one embodiment, the molar ratio is greater than 0.25, or greater than 0.30.

[0112] The inventors have determined that in some embodiments, these ratios are such that the interlaminar shear strength after heat treatment ILSS RTA, measured according to ASTM D2344M-16, is at least 96.5 MPa According to another embodiment, these ratios can provide a final cured composite having an interlaminar shear strength (ILSS TOS) according to ASTM D2344M-16 after heat treatment of at least 82.7 MPa According to yet another embodiment, the cured composite can have an interlaminar shear strength ILSS TOS / ILSS RTA ratio according to ASTM-D2344M-16 of 80% after heat treatment. Details of these measurements according to ASTM-D2344M-16 are described in the Examples herein.

[0113] According to some embodiments, the molar ratio of the comonomer (C) to the bismaleimide compound (B-1) [(C) / (B-1)] may be from 0.20 to 0.45, from 0.25 to 0.40, or from 0.30 to 0.35. Benzoxazine resin composition The benzoxazine resin composition according to the present invention comprises any of the known bismaleimide compounds. In an embodiment, the benzoxazine resin composition is formed by mixing at least one benzoxazine compound (B-2) and at least one epoxy resin having specific structural features. Benzoxazine compound (B-2) The benzoxazine compound (B-2) used in the present invention includes any of the known benzoxazine compounds. In one embodiment, the benzoxazine compound (B-2) includes, consists essentially of, or consists of at least one multifunctional benzoxazine resin containing two or more structural units represented by the following general formula (III):

[0114] [ka]

[0115] In formula (III), R1 represents a linear alkyl group having 1 to 12 carbon atoms, a cyclic alkyl group having 3 to 8 carbon atoms, a phenyl group, or a linear alkyl group having 1 to 12 carbon atoms or a phenyl group substituted with a halogen, and a hydrogen atom is bonded to at least one of the carbon atoms at the ortho and para positions relative to the carbon atom bonded to the aromatic ring oxygen atom.

[0116] In the structural unit represented by the general formula (III), non-limiting examples of R1 include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, a cyclopentyl group, a cyclohexyl group, a phenyl group, an o-methylphenyl group, a m-methylphenyl group, a p-methylphenyl group, an o-ethylphenyl group, a m-ethylphenyl group, a p-ethylphenyl group, an ot-butylphenyl group, a mt-butylphenyl group, a pt-butylphenyl group, an o-chlorophenyl group, an o-bromophenyl group, a dicyclopentadiene group, or a benzofuranone group. Among these groups, the presence of a methyl group, an ethyl group, a propyl group, a phenyl group, or an o-methylphenyl group contributes to favorable handling properties, so it is preferable to use these groups.

[0117] The structural units represented by structural formula (III) may be linked directly (e.g., by a single bond connecting the benzene rings) or via a linker group, in particular a divalent linker group such as -CH2-, -C(CH3)2-, carbonyl, -S-, -SO2-, -O-, or -CH(CH3)-. Such a divalent linker group may be bonded to a carbon atom of a benzene ring of one structural unit of formula (III) and a carbon atom of a benzene ring of another structural unit of formula (III). The structural units of structural formula (III) may also be linked via the nitrogen atom of such structural unit (through the R1 substituent) by a divalent linker group corresponding to the general formula NLN, where L is a divalent linker group and each N is part of an oxazine ring. For example, such a linker group may be -Ar-CH2-Ar-, where Ar is a benzene ring (as exemplified in structural formula (IIIB) and structural formula (XV) below). Other suitable linker groups include -Ar-, -Ar-S-Ar-, and -Ar-O-Ar-, where Ar is a benzene ring.

[0118] Additional difunctional benzoxazine resins suitable for use in the present invention include, for example, those represented by Formula (IA) and Formula (IIIB) below:

[0119] [ka]

[0120] Y is a direct bond, -C(R 3 )(R 4 )-, -C(R 3 )(aryl)-, -C(=O)-, -S-, -O-, -S(=O)-, -S(=O)2-, divalent heterocycles (e.g., 3,3-isobenzofuran-1(3h)-one), and -[C(R3)(R4)] x -Arylene-[C(R5)(R6)] y -, or the two benzyl rings of the benzoxazine moiety may be fused.

[0121] R1 and R2 in formula (IIIA) are each independently an alkyl group (e.g., C1-8 alkyl), cycloalkyl (e.g., C 5-7 cycloalkyl, preferably C cycloalkyl) and aryl, where the cycloalkyl and aryl groups are, for example, C 1-8 It may be substituted by alkyl, halogen and amine groups, and when substituted, one or more substituents (preferably one substituent) may be present on each cycloalkyl and aryl group. R1 and R2 in formula (IIIB) may be independently selected from the same group, and may further be hydrogen.

[0122] R3, R4, R5, and R6 are H, C 1-8 Alkyl (preferably C 1-4 x and y are independently selected from alkyl, preferably methyl, and alkyl halide, where halogen is typically chlorine or fluorine, and x and y are independently 0 or 1. When an arylene group is present, the arylene group is preferably phenylene. In one embodiment, the groups attached to the phenylene group may be configured in the para or meta positions relative to each other. When an aryl group is present, the aryl group is preferably phenyl.

[0123] The group Y may be linear or non-linear, typically linear. The group Y is preferably attached to each benzyl group of the benzoxazine moiety at the para position relative to the oxygen atom of the benzoxazine moiety, as shown in formula (IIIA), which is the preferred isomeric configuration. However, the group Y may be attached to either the meta or ortho position of one or both of the benzyl groups in the bifunctional benzoxazine compound. Thus, the group Y may be attached to the benzyl ring in a para / para, para / meta, para / ortho, meta / meta, or ortho / meta configuration.

[0124] In another embodiment, the bifunctional benzoxazine resin corresponding to formula (IIIA) is selected from compounds where R1 and R2 are independently selected from aryl, preferably phenyl. In one embodiment, the aryl group may be substituted, preferably the substituent(s) are C 1-8 and preferably, there is a single substituent on at least one aryl group. 1-8 Alkyl includes straight and branched alkyl chains. Preferably, R1 and R2 in formula (IIIA) are independently selected from unsubstituted aryl, preferably unsubstituted phenyl.

[0125] The benzyl ring in each benzoxazine group of the bifunctional benzoxazine resin defined herein as formula (IIIA) may be independently substituted at any of the three available positions on each ring, with any one substituent typically being ortho to the attachment position of the Y group, however preferably the benzyl ring remains unsubstituted.

[0126] Suitable trifunctional benzoxazine resins include compounds that can be prepared by reacting an aromatic triamine with a phenol (monohydric or polyhydric) in the presence of an aldehyde, such as formaldehyde, or a source or equivalent thereof.

[0127] In the present disclosure, it is preferable to use at least one monomer represented by the following structural formulas (III) to (XIV) as the polyfunctional benzoxazine compound (B-2).

[0128] [ka]

[0129] [ka]

[0130] [ka]

[0131] In a specific embodiment of the present invention, the benzoxazine resin composition preferably contains (or essentially consists of, or consists of) at least one polyfunctional benzoxazine compound (B-2), which may be composed of a monomer alone or may have the form of an oligomer in which multiple molecules are polymerized. In addition, polyfunctional benzoxazine compounds (B-2) with different structures may be used in combination (i.e., the benzoxazine resin composition may contain two or more polyfunctional benzoxazine compounds (B-2)).

[0132] Benzoxazine compounds (B-2) can be procured from many sources, such as Shikoku Kasei, Konishi Chemical Industry, Huntsman Advanced Materials, etc. Among these sources, Shikoku Kasei supplies bisphenol A-aniline type benzoxazine compounds, bisphenol A methylamine type benzoxazine compounds, and bisphenol F aniline type benzoxazine compounds. Multifunctional benzoxazine compounds can be prepared by reacting phenolic compounds (e.g., bisphenol A, bisphenol F, bisphenol S, thiodiphenol) with aldehydes and arylamines as needed without using commercially available raw materials. Detailed preparation methods can be found in U.S. Pat. Nos. 5,543,516, 4,607,091 (Schreiber), 5,021,484 (Schreiber), and 5,200,452 (Schreiber). Mixture of epoxy resin and benzoxazine compound (B-2) In the present invention, the epoxy resin that can be mixed with the benzoxazine compound (B-2) means an epoxy compound having at least two 1,2-epoxy groups in the molecule, i.e., an epoxy compound that is at least difunctional with respect to the epoxy functional group.

[0133] In certain embodiments of the present invention, the epoxy resin comprises at least one cycloaliphatic epoxy resin represented by formula (XVI), where R1 and R2 are the same or different and are each an aliphatic moiety that together with the carbon atoms of the epoxy group form at least one aliphatic ring (in certain cases, a bicycloaliphatic ring is formed), and X represents a single bond or is a divalent moiety having a molecular weight of less than 45 g / mol. In other embodiments, X is absent in formula (XVI) and the cycloaliphatic epoxy resin comprises a fused ring system comprising R1 and R2, such as in dicyclopentadiene diepoxide.

[0134] [ka]

[0135] Here, the cycloaliphatic epoxy resin means an epoxy resin having at least two 1,2-epoxycycloalkane structural parts (wherein each of the parts is an aliphatic ring in which two adjacent carbon atoms, which are part of the aliphatic ring, are also part of the epoxy ring by being bonded to the same oxygen atom). As mentioned above, cycloaliphatic epoxy resins are useful because they can reduce the viscosity of the resin composition. However, representative cycloaliphatic epoxies such as 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate may also reduce the glass transition temperature and elastic modulus of the cured product. To solve this problem, cycloaliphatic epoxies having shorter bonds between 1,2-epoxycycloalkane groups and higher rigidity or containing condensed ring systems are adopted in the present invention.

[0136] Examples of shorter, more rigid linkages between 1,2-epoxycycloalkane groups in which the divalent moiety has a molecular weight of less than 45 g / mole are oxygen (X=-O-), sulfur (X=-S-), alkylene (e.g., X=-CH-, -CHCH-, -CHCHCH-, -CHCH(CH)-, or -C(CH)-), ether-containing moieties (e.g., X=-CHOCH-), carbonyl-containing moieties (e.g., X=-C(=O)-), or oxirane ring-containing moieties (e.g., X=-CH-O-CH-, where a single bond is between two carbon atoms, thereby forming a three-membered ring containing the oxygen atom and the two carbon atoms).

[0137] In certain embodiments, X in formula (XVI) is absent, which means that R1 and R2 are part of a fused ring system. Dicyclopentadiene dioxide is an example of a cycloaliphatic epoxy resin in which R1 and R2 are part of a fused ring system. In other embodiments, X in formula (XVI) is a single bond connecting the cyclic group including R1 and R2.

[0138] The cycloalkane groups present in such cycloaliphatic epoxy resins may be, for example, monocyclic or bicyclic (e.g., norbornane groups). Examples of suitable monocyclic cycloalkane groups include, but are not limited to, cyclohexane and cyclopentane groups. Such cycloalkane groups may be substituted (e.g., with alkyl groups) or are preferably unsubstituted. When X is a single bond or a divalent moiety having a molecular weight of less than 45 g / mol, the epoxy groups on such cyclohexane and cyclopentane rings may be in the 2,3 or 3,4 positions on the ring.

[0139] The use of cycloaliphatic epoxies having the aforementioned single bonds, divalent moieties having molecular weights less than 45 g / mol, or fused ring systems is advantageous because the rigidity of the molecule increases the elastic modulus of the cured product. Additionally, the inclusion of a divalent moiety (e.g., X is an oxirane ring-containing moiety) that satisfies the aforementioned conditions and is capable of forming covalent bonds with other components of the resin formulation is advantageous because it can increase the crosslink density, thereby improving both the glass transition temperature and the elastic modulus of the cured product.

[0140] Specific illustrative examples of cycloaliphatic epoxy resins used in the present invention include bis(herein, 3,4-epoxycyclohexyl) (also referred to as 3,4,3',4'-diepoxybicyclohexyl when Y is a single bond), bis[(3,4-epoxycyclohexyl)ether] (wherein Y is an oxygen atom), bis[(3,4-epoxycyclohexyl)oxirane] (wherein Y is an oxirane ring, -CH-O-CH-), bis[(3,4-epoxycyclohexyl)methane] (wherein Y is methylene, CH), 2,2-bis(3,4-epoxycyclohexyl)propane (wherein Y is -C(CH)-), and the like, and combinations thereof. In addition, mono- and bicyclopentane-substituted versions of the aforementioned monomers can be used, such as bis(3,4-epoxycyclopentyl), bis(3,4-epoxycyclopentyl)ether, 3,4-epoxycyclopentyl-3,4-epoxycyclohexyl, and the like. thermoplastic In certain embodiments of the present invention, it may be desirable to mix or dissolve at least one thermoplastic compound in the high heat resistance thermosetting resin composition described above in order to enhance the properties of the cured product, increase the minimum viscosity during curing, and improve processing properties. In general, a thermoplastic compound (polymer) having a bond selected from the group consisting of a carbon-carbon bond, an amide bond, an imide bond, an ester bond, an ether bond, a carbonate bond, a urethane bond, a thioether bond, a sulfone bond, and / or a carbonyl bond in the main chain of the thermoplastic compound (polymer) is preferred. Furthermore, the thermoplastic compound may have a partially crosslinked structure and may be crystalline or amorphous. In particular, it is suitable or preferred that at least one thermoplastic compound selected from the group consisting of polyamide, polycarbonate, polyacetal, polyphenylene oxide, polyphenylene sulfide, polyarylate, polyester, polyamideimide, polyimide (including polyimide having a phenyltrimethylindane or phenylindane structure), polyetherimide, polysulfone, polyethersulfone, polyetherketone, polyetheretherketone, polyaramid, polyethernitrile, and polybenzimidazole is mixed or dissolved in the high heat-resistant thermosetting matrix resin composition (B). In the case of a polyimide-based thermoplastic compound, the skeleton of the thermoplastic compound may further contain a phenyltrimethylindane or phenylindane unit.

[0141] In a specific embodiment of the present invention, in order to obtain a preferable heat resistance, the glass transition temperature (Tg) of the thermoplastic substance is 150°C or higher, preferably 170°C or higher, more preferably 200°C or higher, and particularly preferably 220°C or higher. If the glass transition temperature of the thermoplastic substance to be blended is less than 150°C, the molded product obtained will be thermally deformed during use. From the viewpoint of expressing high heat resistance and high solvent resistance, or from the viewpoint of affinity for the high heat-resistant thermosetting resin composition such as solubility and adhesiveness, it is preferable to use polysulfone, polyethersulfone, polyphenylene sulfide, polyimide (including polyimide having a phenyltrimethylindane or phenylindane structure), or polyetherimide.

[0142] Specific examples of suitable sulfone-based thermoplastic compounds include, but are not limited to, polyethersulfone and polyethersulfone-polyetherethersulfone copolymer oligomers as described in U.S. Patent Application Publication No. 2004 / 044141 A1, the contents of which are incorporated herein by reference for all purposes. Specific examples of suitable imide-based thermoplastic compounds include, but are not limited to, polyimide and polyimide-phenyltrimethylindane oligomers as described in U.S. Patent No. 3,856,752, the contents of which are incorporated herein by reference for all purposes.

[0143] As used herein, the term oligomer refers to a relatively low molecular weight polymer in which only about 10 to about 100 monomer molecules are bonded together. In embodiments, the thermoplastic compound is an oligomer.

[0144] The molecular weight of the thermoplastic compound is preferably 150,000 g / mol or less in weight average molecular weight. More preferably, the weight average molecular weight is 7,000 to 150,000 g / mol. The weight average molecular weight is measured using gel permeation chromatography described later. If it is less than 7,000 g / mol, the effect of improving the physical properties is small, and the heat resistance of the high heat resistant thermosetting resin composition is impaired. If the Mw of the thermoplastic compound is more than 150,000 g / mol, the compatibility with the high heat resistant thermosetting resin composition is poor, and the improvement of physical properties is not obtained in the curable or cured high heat resistant thermosetting resin composition or the sizing agent coated carbon fiber reinforced composite material. In addition, when dissolved, the viscosity becomes too high even with a small amount of compounding, and the tackiness and drapeability are reduced when producing a prepreg. When a thermoplastic material having a weight average molecular weight of 7000 to 150000 g / mol is used, the compatibility with the high heat resistant thermosetting resin composition is improved, and the physical properties of the high heat resistant thermosetting resin composition are improved without impairing the heat resistance of the high heat resistant thermosetting resin composition. In addition, the thermoplastic material imparts appropriate tackiness and drapeability when producing a prepreg.

[0145] The weight-average molecular weight and number-average molecular weight of the components used in the present invention can be determined by gel permeation chromatography (hereinafter, "GPC"). The number-average molecular weight of a monomer corresponds to the molecular weight of one monomer unit. Examples of methods for measuring the weight-average molecular weight and number-average molecular weight include a method in which two Shodex80M (registered trademark) [columns] (manufactured by Showa Denko) and one Shodex802 (registered trademark) [column] (manufactured by Showa Denko) are used, 0.3 μL of sample is injected, and the retention time of the sample measured at a flow rate of 1 mL / min is converted to molecular weight using the retention time of a calibration sample made of polystyrene. When multiple peaks are observed by liquid chromatography, the target component is separated in advance by liquid chromatography, and each component is subjected to GPC, and then the molecular weight is converted.

[0146] Although the high heat resistant thermosetting resin composition does not need to contain a thermoplastic compound, in various embodiments of the present invention, the high heat resistant thermosetting resin composition is composed of at least 1, at least 5, or at least 10 parts by weight of the thermoplastic compound. For example, the high heat resistant thermosetting resin composition may be composed of 5 to 30 parts by weight of the thermoplastic compound per 100 parts by weight of the total amount of the high heat resistant thermosetting resin composition. Other additives In certain embodiments, the high heat resistant thermosetting resin composition (B) additionally comprises, additionally consists essentially of, or additionally comprises one or more additional additives. Examples of suitable such additional additives include, but are not limited to, toughening agents, accelerators, reinforcing agents, fillers, adhesion promoters, flame retardants, thixotropic agents, and combinations thereof. Prepreg Prepreg manufacturing Next, the prepreg and the sizing-agent-coated carbon fiber reinforced composite material of the present invention will be described.

[0147] In the present invention, the prepreg contains the sizing-agent-coated carbon fiber or the sizing-agent-coated carbon fiber produced by the above-mentioned method, and a highly heat-resistant thermosetting resin composition (B).

[0148] The prepreg of the present invention is prepared by impregnating a sizing-agent-coated carbon fiber bundle with the highly heat-resistant thermosetting resin composition (B) as a matrix resin. The prepreg can be prepared, for example, by a wet method in which the matrix resin is dissolved in a solvent such as methyl ethyl ketone or methanol to reduce the viscosity and the solution is impregnated into the carbon fiber bundle, or by a hot melt method in which the matrix resin is heated to reduce the viscosity and the carbon fiber bundle is impregnated with the solution.

[0149] In the wet method, the sizing agent-coated carbon fiber bundle is immersed in a solution containing a matrix resin, the carbon fiber bundle is pulled out, and the solvent is evaporated in an oven or other equipment to prepare the carbon fiber bundle.

[0150] In the hot melt method, the prepreg is prepared by a method in which the matrix resin whose viscosity has been reduced by heat is directly impregnated into the sizing-agent-coated carbon fiber bundle, or a method in which a coating of the matrix resin composition is first prepared on release paper or the like, and then the coating is placed on each side or one side of the sizing-agent-coated carbon fiber bundle, and the matrix resin is impregnated into the sizing-agent-coated carbon fiber bundle by applying heat and pressure. The hot melt method is preferred because no solvent remains in the prepreg.

[0151] The cross-sectional density of the sizing agent-coated carbon fiber of the prepreg is 50 to 1000 g / m 2 The cross-sectional density may be at least 50 g / m 2 If the cross-sectional density is 1000 g / m, there may be a need to laminate a small number of prepregs to ensure a predetermined thickness when molding a sizing agent-coated carbon fiber reinforced composite material, and the lamination work can be simplified. 2If it is less than 40%, the drapeability of the prepreg can be good. The mass fraction of the sizing-agent-coated carbon fiber of the prepreg may be 40 to 90% by mass in some embodiments, 50 to 85% by mass in other embodiments, and 60 to 80% by mass in still other embodiments. If the mass fraction of the sizing-agent-coated carbon fiber is at least 40% by mass, the fiber content is sufficient, and the sizing-agent-coated carbon fiber reinforced composite material has the advantage of being excellent in specific strength and specific modulus, and the sizing-agent-coated carbon fiber reinforced composite material can be prevented from excessively generating heat during curing. If the mass fraction of the sizing-agent-coated carbon fiber is 90% by mass or less, the risk of a large number of voids occurring in the sizing-agent-coated carbon fiber reinforced composite material can be reduced, and impregnation with the resin can be satisfied.

[0152] An example of a method for forming a sizing-agent-coated carbon fiber reinforced composite material using the prepreg of the present invention is a method in which the prepregs are laminated and the matrix resin is thermally cured while applying pressure to the laminate.

[0153] In the method of laminating and molding the prepregs, heat and pressure can be applied by any of a press molding method, an autoclave molding method, a bagging molding method, a wrapping tape method, an internal pressure molding method, and the like.

[0154] Autoclave molding is a method in which prepregs are laminated on a tool plate of a predetermined shape, covered with a bagging film, and then cured while removing air from the laminate by applying heat and pressure. The orientation of the fibers can be precisely controlled, and the void content is low, so that a high-quality molding material with excellent mechanical properties can be provided. The pressure applied during the molding process may be in the range of 0.3 to 1.0 MPa, and the molding temperature may be in the range of 90 to 300°C. Due to the exceptionally high Tg of the cured benzoxazine resin composition of the present invention, it may be advantageous to carry out the curing of the prepreg at a relatively high temperature (e.g., a temperature of at least 180°C, or at least 200°C). For example, the molding temperature may be 200°C to 275°C. Alternatively, the prepreg may be molded at a slightly lower temperature (e.g., 90°C to 200°C), demolded, and post-cured at a higher temperature (e.g., 200 to 275°C) after removal from the mold.

[0155] The wrapping tape method is a method in which a prepreg is wound around another core rod such as a mandrel to form a cylindrical sizing agent-coated carbon fiber reinforced composite material. This method can be used to manufacture rod-shaped products such as golf shafts and fishing rods. Specifically, it involves winding a prepreg around a mandrel, winding a wrapping tape made of a thermoplastic film around the prepreg, and applying tension for the purpose of fixing and pressurizing the prepreg. After heating in an oven to harden the resin, the core rod is removed to obtain a cylindrical body. The tension when winding the wrapping tape may be in the range of 20 to 100 N, and the molding temperature may be in the range of 80 to 300°C.

[0156] The internal pressure molding method is a method in which a preform obtained by wrapping a prepreg around an internal pressure applicator such as a thermoplastic resin tube is set in a mold, high pressure gas is introduced into the internal pressure applicator to apply pressure, and the mold is heated at the same time to mold the prepreg. It can be used to mold objects with complex shapes such as golf shafts and bats, tennis and badminton rackets, etc. The pressure applied during the molding process can be 0.1 to 2.0 MPa. The molding temperature can be in the range of room temperature to 300°C, or in the range of 180 to 275°C.

[0157] The sizing-coated carbon fiber reinforced composite material produced from the prepreg of the present invention can have a Class A surface, as described above. A "Class A surface" means a surface that is aesthetically free of blemishes and defects and exhibits extremely high finish quality characteristics.

[0158] The sizing-coated carbon fiber reinforced composite material containing the cured high heat-resistant thermosetting resin composition (B) obtained by curing the curable high heat-resistant thermosetting resin composition (B) according to the embodiment of the present invention and the sizing-coated carbon fiber is advantageously used in sports applications, general industrial applications, and aerospace applications. Examples of sports applications in which these materials are advantageously used include golf shafts, fishing rods, tennis or badminton rackets, hockey sticks, ski poles, etc. Examples of general industrial applications in which these materials are advantageously used include vehicle structural materials such as automobiles, bicycles, ships, and railway cars, drive shafts, leaf springs, windmill blades, pressure vessels, flywheels, papermaking rollers, roofing materials, cables, repair and reinforcement materials, etc.

[0159] Although the embodiments have been described herein in a manner that enables a clear and concise specification to be written, it is intended and will be understood that the embodiments can be variously combined or separated without departing from the invention, For example, it will be understood that all preferred features described herein are applicable to all aspects of the invention described herein.

[0160] In some embodiments, the invention herein can be construed to exclude any element or process step that does not materially affect the basic and novel characteristics of the composition or process. Further, in some embodiments, the invention can be construed to exclude any element or process step not specified herein.

[0161] Although the invention is illustrated and described herein with reference to specific embodiments, it is not intended that the invention be limited to the details shown, but rather, various changes in the details may be made within the scope of the claims and equivalents without departing from the invention.

[0162] The present invention can be summarized according to the following non-limiting aspects. Aspect 1 A prepreg comprising sizing-coated carbon fibers and a thermosetting resin composition (B) impregnated between the sizing-coated carbon fibers, The sizing agent comprises a reactive component (A) containing at least three reactive groups per molecule, the reactive groups being

[0163] (i) two or more first functional groups capable of reacting with the thermosetting resin composition (B); and

[0164] (ii) at least one second functional group different from the two or more first functional groups (i), the second functional group comprising at least one of an amide, an imide, a urethane, a urea, a carbonyl, an ester, a sulfonyl, an aromatic ring, or a combination thereof; The thermosetting resin composition (B) comprises at least one thermosetting resin other than an epoxy resin, and has a glass transition temperature of 220°C or higher after curing.

[0165] Aspect 2. The prepreg of aspect 1, wherein the functional group (i) comprises at least one of an epoxy group, a vinyl group, an acryloyl group, a methacryloyl group, or a combination thereof.

[0166] Aspect 3: The prepreg according to aspect 1 or aspect 2, wherein the component (A) has a urethane group as the second functional group (ii).

[0167] Aspect 4 The prepreg according to any one of aspects 1 to 3, wherein the component (A) contains three or more of the functional groups (i).

[0168] Aspect 5: The prepreg according to any one of aspects 1 to 4, wherein the component (A) has an aromatic ring structure as the functional group (ii).

[0169] Aspect 6 The prepreg of any one of aspects 1 to 5, wherein component (A) has a number average molecular weight of less than 1500 g / mol.

[0170]

[0023] Embodiment 7: The prepreg of any one of embodiments 1-6, wherein the sizing agent comprises at least one accelerator.

[0171] Aspect 8 The prepreg according to any one of Aspects 1 to 7, wherein the surface oxygen concentration (O / C) of the carbon fiber measured by X-ray photoelectron spectroscopy is 0.12 to 0.25.

[0172] Aspect 9: The prepreg according to any one of aspects 1 to 8, wherein the high heat resistant thermosetting resin composition (B) is composed of at least one maleimide compound (B-1) and at least one comonomer (C).

[0173]

[0023] Aspect 10. The prepreg of aspect 9, wherein the comonomer (C) has at least one vinyl group.

[0174]

[0023] Aspect 11. The prepreg of aspect 9 or aspect 10, wherein the comonomer (C) has at least one group selected from a phenol group, a hydroxyl group, and a thiol group.

[0175] Aspect 12 The prepreg according to any one of Aspects 9 to 11, wherein the comonomer (C) has at least one vinyl group and at least one group selected from a phenol group, a hydroxyl group, and a thiol group.

[0176] Aspect 13 The prepreg according to any one of aspects 9 to 12, wherein the molar ratio of (C) / (B-1) is less than 0.5.

[0177] Aspect 14 The prepreg according to any one of aspects 9 to 13, wherein the molar ratio of (C) / (B-1) is greater than 0.2.

[0178] Aspect 15 The prepreg of any one of aspects 1 to 14, wherein the thermosetting resin composition (B) contains at least one benzoxazine compound (B-2).

[0179] Aspect 16 The prepreg according to any one of aspects 1 to 15, wherein the resin composition (B) has a glass transition temperature of 240° C. or higher after curing.

[0180] Aspect 17: A carbon fiber reinforced composite material obtained by curing the prepreg according to any one of aspects 1 to 16.

[0181] Aspect 18 After heat treatment according to ASTM D2344M-16, at least 96.5 MPa 18. The carbon fiber reinforced composite material of embodiment 17, having an interlaminar shear strength ILSS RTA of

[0182] Aspect 19 After heat treatment according to ASTM D2344M-16, at least 82.7 MPa 18. The carbon fiber reinforced composite material of embodiment 17, having an interlaminar shear strength ILSS TOS of.

[0183] Example 20. The carbon fiber reinforced composite material of example 17, having a ratio of interlaminar shear strength ILSS TOS / ILSS RTA of 80% after heat treatment according to ASTM D2344M-16. EXAMPLES

[0184] Hereinafter, the embodiments of the present invention will be described in more detail with reference to examples. Various physical properties were measured by the methods shown below. These properties were measured under environmental conditions including a temperature of 23°C and a relative humidity of 50%, unless otherwise specified. Then, prepregs were produced from the exemplified resins by the hot melt prepreg method. The members used in the examples and comparative examples are as follows. <Carbon fiber> Carbon fiber CF-A (surface oxygen concentration O / C = 0.15, surface roughness (Pa) = 3.0 nm) A copolymer consisting of 99 mol% acrylonitrile and 1 mol% itaconic acid was wet-dry spun and carbonized to obtain a carbon fiber with a total filament count of 24,000, a total fineness of 1,000 tex, a specific gravity of 1.8, a strand tensile strength of 5.9 GPa, and a strand tensile modulus of 295 GPa. Next, this carbon fiber was subjected to an electrolytic surface treatment to adjust the oxygen concentration (O / C) of the surface to 0.15. The electrolytically surface-treated carbon fiber was then washed with water and dried with hot air to obtain a carbon fiber. The obtained carbon fiber was named carbon fiber CF-A. Carbon fiber CF-B (surface oxygen concentration O / C = 0.09, surface roughness (Ra) = 2.9 nm) Carbon fiber was prepared in the same manner as carbon fiber CF-A, except that the surface oxygen concentration (O / C) was adjusted to 0.09 by electrolytic surface treatment. The obtained carbon fiber was named carbon fiber CF-B. Carbon fiber CF-C (surface oxygen concentration O / C = 0.20, surface roughness (Ra) = 3.0 nm) A copolymer consisting of 99 mol% acrylonitrile and 1 mol% itaconic acid was dry-wet spun and sintered to obtain a carbon fiber with a total filament count of 12,000, a total fineness of 505 tex, a specific gravity of 1.8, a strand tensile strength of 6.3 GPa, and a strand tensile modulus of 330 GPa. Next, this carbon fiber was subjected to an electrolytic surface treatment to adjust the oxygen concentration (O / C) of the surface to 0.20. The electrolytically surface-treated carbon fiber was then washed with water and dried with hot air to obtain the raw carbon fiber. The obtained carbon fiber was named carbon fiber CF-C.

[0185] <Carbon fiber coated with sizing agent> (A-1) containing sizing agent-coated carbon fiber CF-

[0186] An aqueous emulsion containing (A-1) was prepared and applied to carbon fiber CF-A by immersion. The carbon fiber was then heat-treated at 230°C for 60 seconds to obtain a sizing agent-coated carbon fiber bundle. The content of the sizing agent was adjusted to 1.5% by mass relative to the sizing agent-coated carbon fiber.

[0187] Sizing agent-coated carbon fiber CF-, containing (A-2), (A-3), (A-4), or (A-5)

[0188] An aqueous emulsion containing (A-2), (A-3), (A-4), or (A-5) was prepared and applied to carbon fiber CF-A by immersion. The carbon fiber was then heat-treated at 230°C for 60 seconds to obtain a sizing agent-coated carbon fiber bundle. The content of the sizing agent was adjusted to 0.5% by mass relative to the sizing agent-coated carbon fiber.

[0189] Sizing agent-coated carbon fiber CF- containing (X-1) and (X-2)

[0190] An aqueous emulsion containing (X-1) or (X-2) was prepared and applied to carbon fiber CF-A by immersion. The carbon fiber was then heat-treated at 230°C for 60 seconds to obtain a sizing agent-coated carbon fiber bundle. The content of the sizing agent was adjusted to 0.5% by mass relative to the sizing agent-coated carbon fiber.

[0191] (A-1) containing sizing agent-coated carbon fiber CF-B Carbon fibers coated with a sizing agent containing (A-1), CF-B, were obtained in the same manner as in the preparation of carbon fibers coated with a sizing agent containing (A-1), CF-A, except that CF-B was used as the carbon fibers.

[0192] Carbon fiber CF-C coated with sizing agent containing (A-1) Carbon fibers coated with a sizing agent containing (A-1), CF-C, were obtained in the same manner as in the preparation of carbon fibers coated with a sizing agent containing (A-1), except that CF-C was used as the carbon fibers.

[0193] Sizing agent-coated carbon fiber CF-C containing (A-2), (A-3), (A-4) or (A-5) Sizing-agent-coated carbon fiber CF-C containing (A-2), (A-3), (A-4) or (A-5) was obtained in the same manner as in the preparation of sizing-agent-coated carbon fiber CF-A containing (A-2), (A-3), (A-4) or (A-5) above, except that CF-C was used as the carbon fiber. <Reaction component (A)> A-1 (Reactive component (A) having an epoxy group and an aromatic ring structure) jER TM 828 (Mitsubishi Chemical Co., Ltd.), diglycidyl ether of bisphenol A, number average molecular weight 380 g / mol A-2 (reaction component (A) having a methacryloyl group and a urethane group) UA101H (manufactured by Kyoeisha Chemical), glycerin dimethacrylate hexamethylene diisocyanate, number average molecular weight 625 g / mol A-3 (reactive component (A) having an acryloyl group and a urethane group) UA306H (manufactured by Kyoeisha Chemical), pentaerythritol triacrylate hexamethylene diisocyanate, number average molecular weight 765 g / mol A-4 (reactive component (A) having an acryloyl group, a urethane group, and an aromatic ring structure) AH600 (manufactured by Kyoeisha Chemical), phenyl glycidyl ether acrylate hexamethylene diisocyanate, number average molecular weight 613 g / mol A-5 (reaction component (A) having an acryloyl group, a urethane group, and an aromatic ring structure) UA101T (manufactured by Kyoeisha Chemical Co., Ltd.), pentaerythritol triacrylate tolylene diisocyanate, number average molecular weight 770 g / mol <Other compounds for sizing agents> X-1 Adduct of bisphenol A with 10 moles of ethylene oxide X-2 Denacol (registered trademark) EX-212 (manufactured by Nagase ChemteX Corporation), 1,6-hexanediol diglycidyl ether <Maleimide compound (B-1)> Compimide® MDAB (Evonik Industries AG), N,N'-4,4'-diphenylmethane-bismaleimide Compimide® TDAB (Evonik Industries AG), N,N'-2,4-toluene-bismaleimide Compimide® 353A (manufactured by Evonik Industries AG), N,N'-4,4'-diphenylmethane-bismaleimide, N,N'-2,4-toluene-bismaleimide, N,N'-2,2,4-trimethylhexane-bismaleimide <Comonomer (C)> Compimide® TM123 (Evonik Industries AG), 4,4′-bis(o-propenylphenoxy)-benzophenone Compimide® TM124 (manufactured by Evonik Industries AG), o,o'-diallyl bisphenol A Compimide® TM124 ether (Evonik Industries AG), 1-prop-2-enoxy-4-[2-(4-prop-2-enoxyphenyl)propan-2-yl]benzene 4,4-DABPS (manufactured by DOYE PHARMA CO.LTD.), 4,4'-sulfonylbis[2-(2-propenyl)]phenol <Thermoplastic material> Matrimid® 9725 (Huntsman Advanced Materials), polyimide

[0194] (1) Strand tensile strength and elastic modulus of carbon fiber bundles The strand tensile strength and strand modulus of the carbon fiber bundle were measured by the test method for resin-impregnated strands described in JIS-R-7608 (2004) according to the following procedure. The resin composition was "Celloxide (registered trademark)" 2021P (manufactured by Daicel Chemical Industries, Ltd.) / boron trifluoride monoethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) / acetone = 100 / 3 / 4 (parts by mass), and the curing conditions were normal pressure, temperature 125 ° C, and 30 minutes. Ten carbon fiber bundles were tested, and the average values ​​were calculated as the strand tensile strength and strand modulus.

[0195] (2) Surface oxygen concentration of carbon fiber (O / C) The surface oxygen concentration (O / C) of the carbon fibers was measured by X-ray photoelectron spectroscopy using the following procedure. First, the dust adhering to the surface of the carbon fibers was removed using a solvent, and the carbon fibers were then cut into pieces of approximately 20 mm each and placed on a copper sample holder. Next, the sample holder was placed in the sample chamber, and the inside of the sample chamber was 1.33 ×10 -6 Pa The X-ray source was AIKα. 1,2 The measurement was performed at a photoelectron takeoff angle of 90°. The peak correction value for the charge during the measurement was C 1s The binding energy of the main peak (peak top) of was set to 284.6 eV. The C1s peak area was calculated by drawing a straight baseline in the range of 282 to 296 eV. 1s The peak area was determined by drawing a straight baseline in the range of 528 to 540 eV. The surface oxygen concentration was calculated using the sensitivity correction value specific to the instrument. 1s Peak area and C 1s The atomic ratio is calculated from the peak area ratio. The X-ray photoelectron spectrometer used was an ESCA-1600 manufactured by Ulvac-Phi, and the sensitivity correction value specific to the device was 2.33.

[0196] (3) Determination of sizing agent content Approximately 2 g of sizing agent-coated carbon fiber bundle was weighed (W1) (to the fourth decimal place) and placed in an electric furnace (volume 120 cm) set at a temperature of 450°C. 3 ) in a nitrogen gas flow of 50 mL / min for 15 minutes to completely pyrolyze the sizing agent. Next, the carbon fiber bundle was transferred to a container in a dry nitrogen gas flow of 20 L / min, cooled for 15 minutes, and then weighed (W2) (four decimal places). The sizing agent content (wt%) was calculated according to the formula (W1-W2) / W1×100(%). The measurement was performed twice, and the average value was taken as the sizing agent content.

[0197] (4) Production of Highly Heat-Resistant Thermosetting Resin Composition (B) A predetermined amount of comonomer (C) and thermoplastic resin were mixed according to the number of parts, and the mixture was heated at 120°C for 1 hour to dissolve the thermoplastic resin. Furthermore, the bismaleimide compound (B-1) was separately melted at 140°C. This mixture and the bismaleimide compound (B-1) were mixed after lowering the temperature to 100°C, and an accelerator was added at 60°C, followed by kneading to prepare a high heat resistance thermosetting resin composition (B). Table 1-4 summarizes the compositions of various exemplary resin compositions and the properties of the resulting cured resins.

[0198] (5) Prepreg manufacturing A prepreg containing a specific sizing agent-coated carbon fiber impregnated with a specific resin composition (B) was prepared. The resin composition (B) obtained in (4) above was applied to a release paper using a knife coater to obtain a resin mass per unit area of ​​52 g / m. 2 Two resin films were prepared. The structure of the carbon fibers coated with a given sizing agent arranged in one direction (mass per unit area: 190 g / m 2 The two aforementioned fabric resin films were superimposed on both sides of a carbon fiber sheet (a prepreg) and heat and pressure were applied at 100°C and 1 atmosphere using a heated roll to impregnate the sizing-coated carbon fibers with the epoxy resin composition, thereby obtaining a prepreg.

[0199] (6) Prepreg hardening The prepreg obtained in (5) above is cut, laminated, vacuum bag molded, and then pressure-treated in an autoclave. 0.14 MPa The mixture was cured under the following curing condition 1 while applying a vacuum until the vacuum exceeded 100%. 0.59 MPa was applied during the initial temperature ramp and maintained throughout the cure cycle, followed by a post cure in a convection oven using cure condition 2 below. Curing conditions 1: 1. The temperature was increased from room temperature to 143°C at a rate of 1.7°C / min.

[0200] 2. Hold at 143°C for 2 hours.

[0201] 3. The temperature was increased from 143°C to 190°C at a rate of 1.7°C / min.

[0202] 4. The temperature was maintained at 190°C for 2 hours.

[0203] The temperature was decreased from 190°C to 30°C at a rate of 5.2°C / min. Curing conditions 2: 1. The temperature was increased from room temperature to 227°C at a rate of 1.7°C / min.

[0204] 2. Hold at 227°C for 4 hours.

[0205] The temperature was decreased from 227°C to 30°C at a rate of 3.2°C / min.

[0206] (7) Measurement of glass transition temperature (Tg) of cured resin by DMA Torsion The resin composition (B) prepared in (4) was discharged into a mold cavity set to a thickness of 2 mm using a metal spacer having a thickness of 2 mm. Next, the resin composition (B) was cured by heat treatment in a convection oven under the above-mentioned curing conditions 1 and 2 to obtain a cured resin plate having a thickness of 2 mm. A test piece having a length of 50 mm and a width of 12.7 mm was cut out from the above-mentioned plate, and Tg measurement was performed in a 1.0 Hz torsion mode by heating at a temperature of 40 ° C. to 350 ° C. at a rate of 5 ° C. / min according to SACMA SRM 18R-94 using a dynamic viscoelasticity measuring device (ARES, manufactured by TA Instruments). Tg is determined by determining the intersection between the tangent of the glass region and the tangent of the transition region from the glass region to the rubber region on the heat storage elastic modulus curve, and the temperature of the intersection is the glass transition temperature, which is generally called G' onset Tg.

[0207] (8) Measurement of interlaminar shear strength at room temperature (ILSS RTA)

[0208] Twelve sheets of 100 mm x 100 mm were cut out from the prepreg obtained in (5), laminated in one direction, and cured by the method in (6) above to obtain a plate of unidirectional carbon fiber reinforced material with a thickness of about 2 mm. A test piece of 25 mm in length and 4.5 mm in width was cut out from the plate. ILSS RTA was measured by a three-point bending test in accordance with ASTM D2344M-16. The measurement was performed with a ratio of span (L) to thickness (d) of the test piece L / d = 4 ± 0.3, and a crosshead speed of the bend tester of 1.27 mm / min. Five samples were measured, and the average value was calculated.

[0209] (9) Measurement of interlaminar shear strength after heat treatment (ILSS TOS) Test pieces were prepared in the same manner as in (8) above and heat-treated in a convection oven at 232°C for 1000 hours. ILSS TOS was determined in the same manner as ILSS RTA.

[0210] The amounts of various prepregs in each example, their qualities, and the mechanical properties of the fiber-reinforced composite materials are summarized in Tables 1 to 4. Examples 1 to 15 in Tables 1 to 3, which are embodiments of the present invention, provided good-quality prepregs with little fuzz and good mechanical properties and TOS. Examples 1 to 15 and Comparative Example 1 In Comparative Example 1, carbon fibers not coated with a sizing agent were used, and in Examples 1 to 15, carbon fibers coated with a sizing agent using reactive compounds (A-1), (A-2), (A-3), (A-4), and (A-5), respectively, were used. The prepreg of Comparative Example 1 had a lot of fluff, but Examples 1 to 15 had little fluff. Examples 1 to 15, Comparative Examples 2 and 3 Comparative Examples 2 and 3 used carbon fibers coated with a sizing agent using (X-1) that did not contain reactive component (A), and Examples 1 to 15 used carbon fibers coated with a sizing agent using reactive compounds (A-1), (A-2), (A-3), (A-4) and (A-5) [containing reactive component (A)], respectively. Compared with Comparative Examples 2 and 3, Examples 1 to 15 show the advantage of containing reactive component (A) in ILSS RTA, ILSS TOS and ILSS TOS / ILSS RTA. Examples 1 to 15, Comparative Examples 4 and 5 In Comparative Examples 4 and 5, carbon fibers coated with a sizing agent using (X-2) [not including any of the second functional group (ii) amide, imide, urethane, urea, carbonyl, ester, sulfonyl, and aromatic ring structures, and combinations thereof] were used, and in Examples 1 to 15, carbon fibers coated with a sizing agent using reactive compounds (A-1), (A-2), (A-3), (A-4), and (A-5) [having the above-mentioned groups] were used. Compared with Comparative Examples 4 and 5, Examples 4 and 5 clearly show the advantages of containing the above-mentioned groups in ILSS TOS and ILSS TOS / ILSS RTA. Examples 1, 6, 4, 5, and 7 Examples 1 and 6 used a reactant (A) having two functional groups, and Examples 4, 5 and 7 used a reactant (A) having three or more first functional groups (i). Compared to Examples 1 and 6, Examples 4, 5 and 7 demonstrate the advantages of using a reactant (A) having three or more functional groups in ILSS RTA and ILSS TOS. Examples 8, 11, 9, 10, and 12 Examples 8 and 11 used a reactant (A) with two functional groups, and Examples 9, 10 and 12 used a reactant (A) with three or more functional groups. Examples 9, 10 and 12, compared to Examples 8 and 11, demonstrate the advantages of using a reactant (A) with three or more functional groups in ILSS RTA and ILSS TOS. Examples 1, 2, 3, and 8 Examples 2 and 3 used sizing-coated carbon fibers with an O / C of less than 0.12, while Examples 1 and 8 used sizing-coated carbon fibers with an O / C of 0.12 or more. Compared with Examples 2 and 3, respectively, Examples 1 and 8 show the advantages of using sizing-coated carbon fibers with a specific O / C in ILSS RTA, ILSS TOS, and ILSS TOS / ILSS RTA. Examples 9 and 13 In Example 9, the molar ratio of (C) / (B-1) was greater than 0.45, and in Example 13, the molar ratio of (C) / (B-1) was less than or equal to 0.45. Example 13, compared to Example 9, demonstrates the advantage of using a specific molar ratio of (C) / (B-1) in ILSS RTA. Examples 13 and 16 Example 16 has a molar ratio of (C) / (B-1) less than 0.21, and Example 13 has a molar ratio of (C) / (B-1) equal to or greater than 0.21. Example 13, compared to Example 16, demonstrates the benefits of using a specific molar ratio of (C) / (B-1) in terms of ILSS TOS and Tg.

[0211] The following table shows those examples and results. The following ranges apply to all results in the following table. Number of reactive groups per molecule Excellent (More preferable) ≧ 4 Good (favorable) ≧3 Fair (requirements) ≧ 2 Bad (out of range) <2 Cured resin Tg Excellent (More preferable) ≧ 260 Good (favorable) ≧ 240 Fair (requirements) ≧ 220 Bad (out of range) <220 ILSS RTA Excellent (More preferable) ≧ 18 Good (favorable) ≧ 16 Fair (requirements) ≧ 14 Poor (out of range) <14 ILSS TOS Excellent (More preferable) ≧ 16 Good (favorable) ≥ 14 Fair (requirements) ≧ 12 Bad (outside range) <12 ILSS TOS / ILSS RTA Excellent (More preferable) ≥ 90% Good (favorable) ≧ 85% Fair (requirements) ≧80% Bad (out of range) <80

[0212] [Table 1]

[0213] [Table 2]

[0214] [Table 3]

[0215] [Table 4]

[0216] It was expected that the ILSS RTA would be improved by using the specific carbon fiber described in the claims. Instead, it was found that when the specific carbon fiber is combined with a thermosetting resin composition having a Tg of 220°C or higher after curing as described in the claims, the ILSS TOS is improved in addition to the ILSS RTA, and the ILSS TOS / ILSS RTA is also increased. Surprisingly, the present invention has been able to achieve high ILSS RTA, ILSS TOS, and ILSS TOS / ILSS RTA.

Claims

1. A prepreg comprising sizing-agent-coated carbon fibers and a thermosetting resin composition (B) impregnated between the sizing-agent-coated carbon fibers, The sizing agent is comprised solely of a reactive component (A) containing at least three reactive groups per molecule, the reactive groups being (i) two or more first functional groups capable of reacting with the thermosetting resin composition (B); and (ii) at least one second functional group different from the two or more first functional groups (i), the second functional group comprising at least one of an amide, an imide, a urethane, a urea, a carbonyl, an ester, a sulfonyl, an aromatic ring, or a combination thereof; The thermosetting resin composition (B) contains at least one thermosetting resin other than an epoxy resin, and has a glass transition temperature of 220° C. or higher after curing.

2. 2. The prepreg of claim 1, wherein the functional group (i) comprises at least one of an epoxy group, a vinyl group, an acryloyl group, a methacryloyl group, or a combination thereof.

3. The prepreg according to claim 1 or 2, wherein the component (A) has a urethane group as the second functional group (ii).

4. The prepreg according to any one of claims 1 to 3, wherein the component (A) contains three or more of the functional groups (i).

5. The prepreg according to any one of claims 1 to 4, wherein the component (A) has an aromatic ring structure as the functional group (ii).

6. The prepreg according to any one of claims 1 to 5, wherein the number average molecular weight of component (A) is less than 1500 g / mol.

7. The prepreg according to any one of claims 1 to 6, wherein the surface oxygen concentration (O / C) of the carbon fiber measured by X-ray photoelectron spectroscopy is 0.12 to 0.

25.

8. The prepreg according to any one of claims 1 to 7, wherein the thermosetting resin composition (B) is composed of at least one maleimide compound (B-1) and at least one comonomer (C).

9. The prepreg of claim 8 , wherein the comonomer (C) has at least one vinyl group.

10. The prepreg according to claim 8 or claim 9, wherein the comonomer (C) has at least one group selected from a phenol group, a hydroxyl group, and a thiol group.

11. The prepreg according to any one of claims 8 to 10, wherein the comonomer (C) has at least one vinyl group and at least one group selected from a phenol group, a hydroxyl group, and a thiol group.

12. The prepreg according to any one of claims 8 to 11, wherein the molar ratio of (C) / (B-1) is less than 0.

5.

13. The prepreg according to any one of claims 8 to 12, wherein the molar ratio of (C) / (B-1) is greater than 0.

2.

14. The prepreg according to any one of claims 1 to 13, wherein the thermosetting resin composition (B) contains at least one benzoxazine compound (B-2).

15. The prepreg according to any one of claims 1 to 14, wherein the resin composition (B) has a glass transition temperature after curing of 240°C or higher.

16. A carbon fiber reinforced composite material obtained by curing the prepreg according to any one of claims 1 to 15.

17. 17. The carbon fiber reinforced composite material of claim 16, having an interlaminar shear strength ILSS RTA of at least 96.5 MPa after heat treatment according to ASTM D2344M-16.

18. 17. The carbon fiber reinforced composite material of claim 16, having an interlaminar shear strength ILSS TOS of at least 82.7 MPa after heat treatment according to ASTM D2344M-16.

19. 17. The carbon fiber reinforced composite material according to claim 16, having an interlaminar shear strength ILSS TOS / ILSS RTA ratio of 80% after heat treatment according to ASTM D2344M-16.

20. A prepreg comprising sizing-agent-coated carbon fibers and a thermosetting resin composition (B) impregnated between the sizing-agent-coated carbon fibers, The sizing agent comprises a reactive component (A) containing at least three reactive groups per molecule, the reactive groups being (i) two or more first functional groups capable of reacting with the thermosetting resin composition (B); and (ii) at least one second functional group different from the two or more first functional groups (i), the second functional group comprising at least one of an amide, an imide, a urethane, a urea, a carbonyl, an ester, a sulfonyl, an aromatic ring, or a combination thereof; The thermosetting resin composition (B) contains at least one thermosetting resin other than an epoxy resin, and has a glass transition temperature of 220°C or higher after curing. The prepreg has a surface oxygen concentration (O / C) of 0.12 to 0.25 of carbon fibers measured by X-ray photoelectron spectroscopy.

21. The prepreg of claim 20, wherein the functional group (i) comprises at least one of an epoxy group, a vinyl group, an acryloyl group, a methacryloyl group, or a combination thereof.

22. A prepreg as described in claim 20 or claim 21, wherein the component (A) has a urethane group as the second functional group (ii).

23. A prepreg described in any of claims 20 to 22, wherein component (A) contains three or more functional groups (i).

24. A prepreg described in any of claims 20 to 23, wherein the component (A) has an aromatic ring structure as a functional group (ii).

25. A prepreg according to any one of claims 20 to 24, wherein the number average molecular weight of component (A) is less than 1500 g / mol.

26. A prepreg described in any of claims 20 to 25, wherein the sizing agent contains at least one accelerator that promotes the formation of covalent bonds between oxygen-containing functional groups on the carbon fiber surface and component (A).

27. ​​A prepreg described in any of claims 20 to 26, wherein the thermosetting resin composition (B) is composed of at least one maleimide compound (B-1) and at least one comonomer (C).

28. The prepreg of claim 27, wherein the comonomer (C) has at least one vinyl group.

29. The prepreg of claim 27 or claim 28, wherein the comonomer (C) has at least one group selected from a phenol group, a hydroxyl group, and a thiol group.

30. A prepreg according to any one of claims 27 to 29, wherein the comonomer (C) has at least one vinyl group and at least one group selected from a phenol group, a hydroxyl group and a thiol group.

31. A prepreg described in any one of claims 27 to 30, wherein the molar ratio of (C) / (B-1) is less than 0.

5.

32. A prepreg described in any one of claims 27 to 31, wherein the molar ratio of (C) / (B-1) is greater than 0.

2.

33. A prepreg described in any of claims 20 to 32, wherein the thermosetting resin composition (B) contains at least one benzoxazine compound (B-2).

34. A prepreg described in any of claims 20 to 33, wherein the glass transition temperature of the resin composition (B) after curing is 240°C or higher.

35. A carbon fiber reinforced composite material obtained by curing the prepreg described in any one of claims 20 to 34.

36. The carbon fiber reinforced composite material of claim 35, having an interlaminar shear strength ILSS RTA of at least 96.5 MPa after heat treatment in accordance with ASTM D2344M-16.

37. The carbon fiber reinforced composite material of claim 35, having an interlaminar shear strength ILSS TOS of at least 82.7 MPa after heat treatment in accordance with ASTM D2344M-16.

38. The carbon fiber reinforced composite material of claim 35, having an interlaminar shear strength ILSS TOS / ILSS RTA ratio of 80% after heat treatment in accordance with ASTM D2344M-16.

Citation Information

Patent Citations

  • Carbon fiber bundle

    JP1994002274A

  • Sizing agent for carbon fiber, sizing of carbon fiber, sizing-treated carbon fiber, sheets from the sized carbon fiber, and fiber-reinforced composite material

    JP2001003266A

  • Carbon fiber-reinforced composite material

    JP2008106245A

  • Sizing agent-applied carbon fiber

    JP2013127132A

  • Sizing agent-coated carbon fibers, method for producing the same, and carbon fiber-reinforced composite material

    JP2015007300A